Binder composition for non-aqueous secondary battery electrodes, slurry composition for non-aqueous secondary battery electrodes, electrodes for non-aqueous secondary batteries, and non-aqueous secondary batteries
Patent Information
- Application Number
- JP2021567344
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-27
- Filing Date
- 2020-12-16
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2040-12-16
Smart Images

Figure 0007639700000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a binder composition for a non-aqueous secondary battery electrode, a slurry composition for a non-aqueous secondary battery electrode, an electrode for a non-aqueous secondary battery, and a non-aqueous secondary battery. [Background technology]
[0002] Non-aqueous secondary batteries such as lithium ion secondary batteries are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and are used in a wide range of applications. Therefore, in recent years, improvements in battery components such as electrodes have been studied in order to further improve the performance of non-aqueous secondary batteries.
[0003] Here, an electrode used in a non-aqueous secondary battery such as a lithium ion secondary battery (hereinafter, sometimes simply abbreviated as "secondary battery") usually includes a current collector and an electrode mixture layer (positive electrode mixture layer or negative electrode mixture layer) formed on the current collector. This electrode mixture layer is formed, for example, by applying a slurry composition containing an electrode active material and a binder composition containing a binding agent onto the current collector and drying the applied slurry composition.
[0004] Therefore, in recent years, attempts have been made to improve the slurry composition used in forming the electrode mixture layer in order to achieve further improvements in the performance of secondary batteries. For example, Patent Document 1 describes that a plasticizer can be added to a binder resin for secondary battery electrodes, the binder resin containing, as constituent units, 50 to 99.99 mol % of vinyl cyanide units and 0.01 to 10 mol % of units having an acidic group and a polymer having a mass average molecular weight of 200,000 or more and 2,000,000 or less, in order to improve the flexibility of the electrodes. Furthermore, Patent Document 2 describes that a plasticizer can be added to a binder resin for a non-aqueous secondary battery electrode, the binder resin containing a polymer in which a polymer containing a vinyl cyanide monomer unit is grafted as a branch polymer onto a polyolefin trunk polymer, and a polymer having an acidic group, in order to improve the flexibility of the electrode. Furthermore, Patent Documents 3 and 4 propose using polyvinylidene fluoride as a binder in combination with a plasticizer when preparing a positive electrode slurry or a positive electrode paste. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2015-213049 A [Patent Document 2] JP 2017-16890 A [Patent Document 3] China Patent Application Publication No. 109841835 [Patent Document 4] China Patent Application Publication No. 108321360 Summary of the Invention [Problem to be solved by the invention]
[0006] In recent years, there has been a demand for secondary batteries to have improved battery characteristics such as rate characteristics and cycle characteristics (hereinafter, sometimes simply referred to as "battery characteristics"). In order to produce a secondary battery with excellent battery characteristics, it is important that the electrodes used exhibit high flexibility and uniformity. However, with the conventional binder resins, positive electrode slurries, and positive electrode pastes described above, it was not possible to simultaneously form an electrode having excellent flexibility and uniformity and improve the rate characteristics and cycle characteristics of a secondary battery including the obtained electrode at a high level.
[0007] Therefore, an object of the present invention is to provide a binder composition for non-aqueous secondary battery electrodes and a slurry composition for non-aqueous secondary battery electrodes, which can simultaneously form an electrode having excellent flexibility and uniformity, and improve the rate characteristics and cycle characteristics of a secondary battery including the obtained electrode, at a high level. Another object of the present invention is to provide an electrode for a non-aqueous secondary battery that is excellent in flexibility and uniformity and can improve the rate characteristics and cycle characteristics of the secondary battery. It is yet another object of the present invention to provide a nonaqueous secondary battery that is excellent in rate characteristics and cycle characteristics. [Means for solving the problem]
[0008] The present inventors have conducted extensive research with the aim of solving the above problems, and have found that the above problems can be advantageously solved by using a binder composition for a non-aqueous secondary battery electrode, the binder composition including a binder component including two types of polymers that satisfy a predetermined composition, a plasticizer, and an organic solvent, and have completed the present invention.
[0009] That is, the present invention has an object to advantageously solve the above-mentioned problems, and the binder composition for a non-aqueous secondary battery electrode of the present invention is a binder composition for a non-aqueous secondary battery electrode, comprising polymer α and polymer β as binder components, a plasticizer, and an organic solvent, wherein the polymer α is an insoluble polymer comprising a (meth)acrylic acid ester monomer unit and an ethylenically unsaturated acid monomer unit, and the polymer β is a readily soluble polymer comprising a nitrile group-containing monomer unit and at least one of an amide group-containing monomer unit and a (meth)acrylic acid ester monomer unit having an alkyl chain carbon number of 1 to 6, and wherein the content of the nitrile group-containing monomer unit is 70% by mass or more and 95% by mass or less, and the total content of the amide group-containing monomer unit and the (meth)acrylic acid ester monomer unit is 0.1% by mass or more and 20% by mass or less, relative to the total of all monomer units constituting the polymer β being 100% by mass. In this way, the binder composition containing the polymers α and β and a plasticizer can simultaneously form an electrode having excellent flexibility and uniformity, and improve the rate characteristics and cycle characteristics of a secondary battery including the obtained electrode at a high level. In this specification, "(meth)acrylic" means acrylic or methacrylic. The type of monomer unit contained in a certain polymer and the "proportion of monomer units" in a certain polymer are defined as follows: 1 It can be identified or measured using a nuclear magnetic resonance (NMR) method such as H-NMR. Furthermore, "containing a monomer unit" means that "a polymer obtained using that monomer contains a repeating unit derived from the monomer." Furthermore, whether a certain polymer is "insoluble" or "easily soluble" can be determined by the method described in the Examples.
[0010] Here, in the binder composition for a non-aqueous secondary battery electrode of the present invention, the content a of the polymer α is preferably 5% by mass or more and 60% by mass or less, and the content b of the polymer β is preferably 20% by mass or more and 94% by mass or less, where the total mass of the binder components is taken as 100% by mass. By setting the contents of the polymers α and β within the above ranges, respectively, the peel strength of the obtained electrode can be increased, and the cycle characteristics of the obtained secondary battery can be further improved.
[0011] In addition, in the binder composition for a non-aqueous secondary battery electrode of the present invention, the polymer α and the polymer β are preferably polymers satisfying the following requirement: when an N-methyl-2-pyrrolidone mixed solution having a solid content concentration of 8 mass % containing the polymer α at the content rate a and the polymer β at the content rate b as solid contents is prepared, the ratio of the insoluble content in the mixed solution is 30 mass % or more and 80 mass % or less. If the insoluble content in N-methyl-2-pyrrolidone of the mixture of the polymers α and β is within the above range, the peel strength of the obtained electrode can be increased, and the cycle characteristics of the obtained secondary battery can be further improved. The "proportion of the insoluble content" can be measured by the method described in the Examples.
[0012] In addition, the binder composition for non-aqueous secondary battery electrodes of the present invention preferably has a plasticizer content of 0.1% by mass or more and 30% by mass or less, where the total mass of the plasticizer and the binder components is 100% by mass. If the plasticizer content relative to the total mass of the binder components is equal to or more than the lower limit, the flexibility of the resulting electrode can be further improved. If the plasticizer content is equal to or less than the upper limit, the peel strength of the resulting electrode can be increased, and the cycle characteristics of a secondary battery including such an electrode can be further improved.
[0013] In the binder composition for non-aqueous secondary battery electrodes of the present invention, the plasticizer preferably has a molecular weight of 1000 or less and a decomposition potential of 3.5 V or more. If the plasticizer has a molecular weight of 1000 or less and a decomposition potential of 3.5 V or more, the flexibility of the obtained electrode can be further improved, and the rate characteristics and cycle characteristics of the obtained secondary battery can be further improved. The molecular weight and decomposition potential of the plasticizer can be measured by the method described in the Examples.
[0014] In addition, the binder composition for a non-aqueous secondary battery electrode of the present invention preferably further contains, as the binder component, a polymer γ, which is an easily soluble polymer having an iodine value of 5 g / 100 g or more and 100 g / 100 g or less. If the binder component further contains a polymer γ, which is an easily soluble polymer having an iodine value within the above range, the flexibility and uniformity of the obtained electrode can be further improved. Furthermore, if the binder component contains polymer γ, the peel strength of the obtained electrode can be increased. The "iodine value" of the polymer γ can be measured by the method described in the Examples.
[0015] In addition, in the binder composition for a non-aqueous secondary battery electrode of the present invention, the content c of the polymer γ is preferably 0.1% by mass or more and 50% by mass or less, based on 100% by mass of the binder component. If the content of the polymer γ in the binder component is within the above range, the flexibility and uniformity of the obtained electrode can be further improved.
[0016] The present invention also aims to advantageously solve the above problems, and the slurry composition for non-aqueous secondary battery electrodes of the present invention is characterized by comprising any one of the binder compositions for non-aqueous secondary battery electrodes described above, an electrode active material, and a conductive material. In this way, according to the slurry composition containing the binder composition for non-aqueous secondary battery electrodes, which contains a binder component containing two types of polymers satisfying the above-mentioned predetermined composition, a plasticizer, and an organic solvent, an electrode active material, and a conductive material, it is possible to simultaneously form an electrode having excellent flexibility and uniformity, and to improve the rate characteristics and cycle characteristics of a secondary battery equipped with the obtained electrode at a high level.
[0017] In the slurry composition for a non-aqueous secondary battery electrode of the present invention, the conductive material preferably contains carbon nanotubes. By blending carbon nanotubes in the slurry composition of the present invention, the rate characteristics of the obtained secondary battery can be further improved.
[0018] The present invention also aims to advantageously solve the above-mentioned problems, and provides an electrode for a non-aqueous secondary battery, comprising an electrode mixture layer containing polymer α and polymer β as binder components, a plasticizer, an electrode active material, and a conductive material, wherein the polymer α is a particulate polymer containing (meth)acrylic acid ester monomer units and ethylenically unsaturated acid monomer units, and the polymer β is an easily soluble polymer containing nitrile group-containing monomer units and at least one of amide monomer units and (meth)acrylic acid ester monomer units having an alkyl chain carbon number of 1 to 6, and the content of the nitrile group-containing monomer units is 70% by mass or more and 95% by mass or less, and the total content of the amide group-containing monomer units and the (meth)acrylic acid ester monomer units is 0.1% by mass or more and 20% by mass or less, relative to the total of all monomer units constituting the polymer β being 100% by mass. A non-aqueous secondary battery electrode containing a binder component including two types of polymers satisfying a predetermined composition, a plasticizer, an electrode active material, and a conductive material is excellent in flexibility and uniformity itself, and can improve the rate characteristics and cycle characteristics of the secondary battery.
[0019] Here, the non-aqueous secondary battery electrode of the present invention preferably further contains, as the binder component, polymer γ, which is an easily soluble polymer having an iodine value of 5 g / 100 g or more and 100 g / 100 g or less. If the non-aqueous secondary battery electrode further contains, as the binder component, polymer γ, which is an easily soluble polymer having an iodine value within the above range, the rate characteristics of a secondary battery including such an electrode can be further improved.
[0020] Furthermore, the present invention aims to advantageously solve the above problems, and the nonaqueous secondary battery of the present invention is characterized by comprising a nonaqueous secondary battery electrode having an electrode mixture layer formed using any of the above-mentioned slurry compositions for nonaqueous secondary battery electrodes. Alternatively, the nonaqueous secondary battery of the present invention is characterized by comprising any of the above-mentioned electrodes for nonaqueous secondary batteries. In this way, by using a nonaqueous secondary battery electrode having an electrode mixture layer formed using any of the above-mentioned slurry compositions for nonaqueous secondary battery electrodes, or any of the above-mentioned electrodes for nonaqueous secondary batteries, a nonaqueous secondary battery having excellent rate characteristics and cycle characteristics can be provided. Effect of the Invention
[0021] According to the present invention, it is possible to provide a binder composition for a non-aqueous secondary battery electrode and a slurry composition for a non-aqueous secondary battery electrode, which can simultaneously achieve, at a high level, the formation of an electrode having excellent flexibility and uniformity, and the improvement of the rate characteristics and cycle characteristics of a secondary battery including the obtained electrode. Furthermore, according to the present invention, it is possible to provide an electrode for a non-aqueous secondary battery, which has excellent flexibility and uniformity and can improve the rate characteristics and cycle characteristics of the secondary battery. Furthermore, according to the present invention, a nonaqueous secondary battery having excellent rate characteristics and cycle characteristics can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Hereinafter, an embodiment of the present invention will be described in detail. Here, the binder composition for non-aqueous secondary battery electrodes of the present invention can be used when preparing a slurry composition for non-aqueous secondary battery electrodes. In addition, the slurry composition for non-aqueous secondary battery electrodes prepared using the binder composition for non-aqueous secondary battery electrodes of the present invention can be suitably used when forming electrodes for non-aqueous secondary batteries such as lithium ion secondary batteries. Furthermore, the non-aqueous secondary battery of the present invention is characterized by using the electrode for non-aqueous secondary batteries of the present invention. The binder composition for a non-aqueous secondary battery electrode and the slurry composition for a non-aqueous secondary battery electrode of the present invention can be particularly suitably used when forming a positive electrode for a non-aqueous secondary battery.
[0023] (Binder composition for secondary battery electrodes) The binder composition for non-aqueous secondary battery electrodes of the present invention is a binder composition for non-aqueous secondary battery electrodes, which comprises polymer α and polymer β as binder components, a plasticizer, and an organic solvent. The binder composition is characterized in that the polymer α is an insoluble polymer containing a (meth)acrylic acid ester monomer unit and an ethylenically unsaturated acid monomer unit, the polymer β is a readily soluble polymer containing a nitrile group-containing monomer unit and at least one of an amide group-containing monomer unit and a (meth)acrylic acid ester monomer unit having an alkyl chain carbon number of 1 to 6, and the content of the nitrile group-containing monomer unit is 70% by mass to 95% by mass, and the total content of the amide group-containing monomer unit and the (meth)acrylic acid ester monomer unit is 0.1% by mass to 20% by mass, where the total of all monomer units constituting the polymer β is 100% by mass. Furthermore, the binder composition for non-aqueous secondary battery electrodes of the present invention preferably contains, as a binder component, a polymer γ, which is a polymer having a predetermined property, in addition to the above-mentioned polymers α and β. Furthermore, the binder composition for non-aqueous secondary battery electrodes of the present invention may contain other binder components that are different from the above-mentioned binder components. The other binder components do not include polymers that can be included in the polymers α to γ.
[0024] Here, the binder composition for non-aqueous secondary battery electrodes of the present invention (hereinafter also simply referred to as "binder composition") contains polymers α and β that satisfy the above composition and property conditions, and a plasticizer, and therefore can form an electrode with excellent flexibility and uniformity, and can improve the rate characteristics and cycle characteristics of a secondary battery equipped with the obtained electrode. The reason for this is not clear, but is presumed to be as follows.
[0025] First, the polymer α, which is insoluble in an organic solvent, in other words, a polymer that exists in the form of particles in an organic solvent and in the formed electrode, can function to effectively bond the components to be bonded together while maintaining the flexibility of the electrode by point-bonding to the components to be bonded, such as the electrode active material, in the electrode mixture layer. Therefore, the polymer α can contribute to increasing the flexibility of the formed electrode mixture layer. In addition, the polymer β contributes to imparting an appropriate viscosity to the slurry composition when the slurry composition is prepared. Therefore, the polymer β contributes to increasing the uniformity and peel strength of the electrode obtained using such a slurry composition, and acts to relieve the concentration of stress and resistance in the electrode, thereby improving the rate characteristics and cycle characteristics of the resulting secondary battery. Furthermore, the plasticizer can function to increase the flexibility of the obtained electrode, and thus to increase the rate characteristics and cycle characteristics of the secondary battery. This is thought to be due to the plasticizer acting to reduce the crystallinity and glass transition temperature of the polymer α and polymer β. Here, when a conventional binder component such as polyvinylidene fluoride and a plasticizer are combined instead of the polymer β, the active material is deteriorated, and battery characteristics such as cycle characteristics and rate characteristics are deteriorated. However, in the present invention, when the polymers α and β having the predetermined composition and properties are combined with a plasticizer, an electrode having high flexibility and uniformity can be obtained, and battery characteristics such as rate characteristics and cycle characteristics can be effectively improved.
[0026] <Polymer α> The polymer α is a component that holds the components contained in the electrode mixture layer from being detached from the electrode mixture layer in an electrode manufactured by forming an electrode mixture layer on a current collector using a slurry composition containing a binder composition (i.e., functions as a binder). The polymer α is an insoluble polymer that is insoluble in an organic solvent, and is a particulate polymer that exists in particulate form in the organic solvent and in the formed electrode. Whether the polymer α is insoluble in an organic solvent and is "particulate" in the electrode can be confirmed according to the method described in the Examples. The polymer α is "insoluble" in an organic solvent means that the dry mass of the insoluble portion obtained by leaving the dried polymer α in N-methyl-2-pyrrolidone at a temperature of 60°C for 72 hours and filtering through a 200 mesh is 70% by mass or more with respect to the total mass of the dried polymer α used. The polymer α is a component that exerts an adhesive ability by point-bonding to an adherend in the electrode. For this reason, the polymer α can increase the flexibility of the electrode while exerting its adhesive ability in the electrode.
[0027] [Composition of polymer α] The polymer α must contain, as repeating units, a (meth)acrylic acid ester monomer unit and an ethylenically unsaturated acid monomer unit. In addition, the polymer α may optionally contain, as repeating units, a crosslinkable monomer unit and other monomer units other than those mentioned above.
[0028] [(Meth)acrylic acid ester monomer unit] The (meth)acrylic acid ester monomer unit is a repeating unit derived from a (meth)acrylic acid ester monomer. When the polymer α contains the (meth)acrylic acid ester monomer unit, the peel strength of the obtained electrode mixture layer can be increased, and the rate characteristics of the obtained secondary battery can be improved.
[0029] The (meth)acrylic acid ester monomer may be a (meth)acrylic acid alkyl ester monomer having one ethylenically unsaturated bond. The (meth)acrylic acid alkyl ester monomer may be one having a linear alkyl group or one having a branched alkyl group. Examples of the (meth)acrylic acid ester monomer include acrylic acid alkyl esters such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, t-butyl acrylate, pentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, 2-ethylhexyl acrylate, nonyl acrylate, decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, and stearyl acrylate; and methacrylic acid alkyl esters such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, t-butyl methacrylate, pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, 2-ethylhexyl methacrylate, nonyl methacrylate, decyl methacrylate, lauryl methacrylate, n-tetradecyl methacrylate, and stearyl methacrylate. Among these, from the viewpoint of imparting an appropriate affinity with the electrolyte to the resulting electrode mixture layer, (meth)acrylic acid alkyl esters having a linear alkyl chain are preferred, and butyl acrylate and methyl methacrylate are more preferred. These may be used alone or in combination of two or more.
[0030] The content of the (meth)acrylic acid ester monomer unit in the polymer α is preferably 30.0 mass% or more, more preferably 40.0 mass% or more, and even more preferably 50.0 mass% or more, and preferably 98.0 mass% or less, and more preferably 95.0 mass% or less, based on 100.0 mass% of all repeating units contained in the polymer α. By setting the content of the (meth)acrylic acid ester monomer unit in the polymer α within the above range, it is possible to impart an appropriate affinity with the electrolyte to the obtained electrode mixture layer, and it is possible to improve the rate characteristics of a secondary battery including such an electrode mixture layer.
[0031] [Ethylenically unsaturated acid monomer unit] The ethylenically unsaturated acid monomer unit is a repeating unit derived from an ethylenically unsaturated acid monomer. Since the polymer α contains an ethylenically unsaturated acid monomer unit, it can exhibit excellent binding strength. Therefore, the electrode mixture layer formed using the slurry composition containing the binder composition of the present invention can exhibit even better peel strength. In this specification, the "ethylenically unsaturated acid monomer unit" is a unit derived from a monomer containing an ethylenically unsaturated bond and an acidic group.
[0032] Here, examples of the ethylenically unsaturated acid monomer capable of forming the ethylenically unsaturated acid monomer unit include, in addition to an ethylenically unsaturated bond, a monomer having a carboxylic acid group, a monomer having a sulfonic acid group, and a monomer having a phosphoric acid group.
[0033] Examples of the carboxylic acid group-containing monomer include monocarboxylic acids and their derivatives, dicarboxylic acids and their acid anhydrides, and their derivatives. Examples of the monocarboxylic acid include acrylic acid, methacrylic acid, and crotonic acid. Examples of the monocarboxylic acid derivatives include 2-ethylacrylic acid, isocrotonic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid, and α-chloro-β-E-methoxyacrylic acid. The dicarboxylic acids include maleic acid, fumaric acid, and itaconic acid. Examples of dicarboxylic acid derivatives include methylmaleic acid, dimethylmaleic acid, phenylmaleic acid, chloromaleic acid, dichloromaleic acid, fluoromaleic acid, and maleic acid monoesters such as nonyl maleate, decyl maleate, dodecyl maleate, octadecyl maleate, and fluoroalkyl maleate. Examples of the acid anhydrides of dicarboxylic acids include maleic anhydride, acrylic anhydride, methylmaleic anhydride, and dimethylmaleic anhydride. Furthermore, as the carboxylic acid group-containing monomer, an acid anhydride which generates a carboxyl group upon hydrolysis can also be used.
[0034] Examples of sulfonic acid group-containing monomers include styrene sulfonic acid, vinyl sulfonic acid, methyl vinyl sulfonic acid, (meth)allyl sulfonic acid, 3-allyloxy-2-hydroxypropanesulfonic acid, and 2-acrylamido-2-methylpropanesulfonic acid. In the present invention, "(meth)allyl" means allyl and / or methallyl.
[0035] Furthermore, examples of the phosphate group-containing monomer include 2-(meth)acryloyloxyethyl phosphate, methyl-2-(meth)acryloyloxyethyl phosphate, and ethyl-(meth)acryloyloxyethyl phosphate. In the present invention, "(meth)acryloyl" means acryloyl and / or methacryloyl.
[0036] These ethylenically unsaturated acid monomers may be used alone or in combination of two or more. Among these ethylenically unsaturated acid monomers, from the viewpoint of further improving the peel strength of the resulting electrode mixture layer, acrylic acid, methacrylic acid, itaconic acid, maleic acid, and fumaric acid are preferred, and acrylic acid and methacrylic acid are more preferred.
[0037] The content of the ethylenically unsaturated acid monomer unit in the polymer α is preferably 1.0% by mass or more, more preferably 1.5% by mass or more, more preferably 2.0% by mass or more, even more preferably 3.0% by mass or more, preferably 10.0% by mass or less, more preferably 8.0% by mass or less, even more preferably 6.0% by mass or less, and even more preferably 5.0% by mass or less, when the total repeating units in the polymer α are taken as 100.0% by mass. By setting the content of the ethylenically unsaturated acid monomer unit to the above lower limit or more, the peel strength of the electrode mixture layer formed using the slurry composition containing the binder composition can be increased. In particular, by setting the content of the ethylenically unsaturated acid monomer unit to the above upper limit or less, the flexibility of the polymer α can be improved, and the peel strength of the obtained electrode mixture layer can be further improved.
[0038] [Cross-linking monomer unit] The crosslinkable monomer unit is a repeating unit derived from a crosslinkable monomer. The crosslinkable monomer is a monomer that can form a crosslinked structure when polymerized. If the polymer α contains a crosslinkable monomer unit, the peel strength of the resulting electrode mixture layer can be further increased. An example of the crosslinkable monomer is a monomer having two or more reactive groups per molecule.
[0039] More specifically, the crosslinkable monomer may be a polyfunctional ethylenically unsaturated carboxylic acid ester monomer having two or more ethylenically unsaturated bonds.
[0040] Examples of bifunctional ethylenically unsaturated carboxylic acid ester monomers having two ethylenically unsaturated bonds in the molecule include allyl acrylate, allyl methacrylate, ethylene diacrylate, ethylene dimethacrylate, 2-hydroxy-3-acryloyloxypropyl methacrylate, polyethylene glycol diacrylate, propoxylated ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A diacrylate, 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, propoxylated bisphenol A diacrylate, tricyclodecane dimethanol diacrylate, 1,10-decanediol diacrylate, 1,6-hexanediol diacrylate, 1,2-dimethylphenyl diacrylate, 1,3-dimethylphenyl diacrylate, 1,4-dimethylphenyl diacrylate, 1,5-dimethylphenyl diacrylate, 1,6-dimethylphenyl diacrylate, 1,7-dimethylphenyl diacrylate, 1,8-dimethylphenyl diacrylate, 1,9-dimethylphenyl diacrylate, 1,8-dimethylphenyl diacrylate, 1,9-dimethylphenyl diacrylate, 1,10-dimethylphenyl diacrylate, 1,2-dimethylphenyl diacrylate, 1,3-dimethylphenyl diacrylate, 1,4-dimethylphenyl diacrylate, 1,5-dimethylphenyl diacrylate, 1,6-dimethylphenyl diacrylate, 1,7-dimethylphenyl diacrylate, 1,8-dimethylphenyl diacrylate, 1,9 ...9-dimethylphenyl diacrylate, 1,9-dimethylphenyl diacrylate, 1,9-dimethylphenyl di ,9-nonanediol diacrylate, polypropylene glycol diacrylate, polypropylene glycol dimethacrylate, polytetramethylene glycol diacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, ethoxylated bisphenol A dimethacrylate, tricyclodecane dimethanol dimethacrylate, 1,10-decanediol dimethacrylate, 1,6-hexanediol dimethacrylate, 1,9-nonanediol dimethacrylate, neopentyl glycol dimethacrylate, ethoxylated polypropylene glycol dimethacrylate, and glycerin dimethacrylate.
[0041] Examples of trifunctional ethylenically unsaturated carboxylic acid ester monomers having three ethylenically unsaturated bonds in the molecule include ethoxylated isocyanuric acid triacrylate, ε-caprolactone-modified tris-(2-acryloxyethyl)isocyanurate, ethoxylated glycerin triacrylate, pentaerythritol triacrylate, trimethylolpropane triacrylate, and trimethylolpropane trimethacrylate.
[0042] Examples of the tetrafunctional or higher ethylenically unsaturated carboxylic acid ester monomer having four or more ethylenically unsaturated bonds in the molecule include ditrimethylolpropane tetraacrylate, ethoxylated pentaerythritol tetraacrylate, pentaerythritol tetraacrylate, dipentaerythritol polyacrylate, and dipentaerythritol hexaacrylate.
[0043] Among these, from the viewpoint of improving the peel strength and flexibility of the obtained electrode mixture layer, allyl methacrylate (bifunctional), ethylene glycol dimethacrylate (bifunctional), trimethylolpropane triacrylate (trifunctional), and ethoxylated pentaerythritol tetraacrylate (tetrafunctional) are preferred.
[0044] The content of the crosslinkable monomer unit in the polymer α is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.1% by mass or more, preferably 5.0% by mass or less, more preferably 2.0% by mass or less, and even more preferably 1.5% by mass or less, based on 100.0% by mass of the total repeating units contained in the polymer α. By setting the content of the crosslinkable monomer unit in the polymer α to the above lower limit or more, the peel strength of the obtained electrode mixture layer can be further improved. In addition, by setting the content of the crosslinkable monomer unit in the polymer α to the above upper limit or less, the flexibility of the obtained electrode mixture layer can be improved, and thus the peel strength of the obtained electrode mixture layer can be further improved.
[0045] [Other monomer units] Furthermore, the polymer α may contain other monomer units derived from other monomers copolymerizable with the various monomers described above. As other monomers capable of forming such other monomer units, known monomers that can be used in the manufacture of binding components in the binder composition for electrodes of non-aqueous secondary batteries can be used. More specifically, for example, other monomers include nitrile group-containing monomers and amide group-containing monomers described in detail in the section on <Polymer β>, and aromatic vinyl monomers described in detail in the section on <Polymer γ>. These can be used alone or in combination of two or more kinds.
[0046] The content of other monomer units in polymer α is preferably 50.0% by mass or less, and may be 0.0% by mass, when the total amount of all repeating units in polymer α is 100.0% by mass.
[0047] [NMP insoluble amount] Here, the insoluble content when the polymer α is mixed with N-methyl-2-pyrrolidone at a concentration of 8% by mass must be 70% by mass or more, preferably 80% by mass or more, more preferably 90% by mass or more, and may be 100% by mass, that is, the polymer α may be completely insoluble in N-methyl-2-pyrrolidone (hereinafter sometimes abbreviated as "NMP"). If the NMP insoluble content is 70% by mass or more, the battery characteristics of the secondary battery including the obtained electrode mixture layer can be further improved. The NMP insoluble content can be controlled by adjusting the blending amount of the crosslinkable monomer in the monomer composition used to prepare the polymer α. The NMP insoluble content of the polymer α can be measured by the method described in the Examples.
[0048] [Method for preparing polymer α] The method for preparing the polymer α is not particularly limited. The polymerization mode for preparing the polymer α is not particularly limited, and any method such as solution polymerization, suspension polymerization, bulk polymerization, or emulsion polymerization can be used. In addition, any reaction such as ionic polymerization, radical polymerization, or living radical polymerization can be used as the polymerization reaction. In addition, emulsifiers, dispersants, polymerization initiators, chain transfer agents, and the like that can be used in polymerization can be those that are generally used.
[0049] <Polymer β> The polymer β is a component that can impart appropriate viscosity to the slurry composition when the slurry composition is prepared. The polymer β is a component that can function as a binder together with the polymer α in the electrode mixture layer. The polymer β is a component that is easily soluble in the organic solvent that constitutes the binder composition. The polymer β is "easily soluble" in the organic solvent means that the dry mass of the insoluble portion obtained by leaving the dried polymer β in N-methyl-2-pyrrolidone at a temperature of 60° C. for 72 hours and filtering through a 200 mesh is 50% by mass or less with respect to the total mass of the dried polymer β used. The polymer β is a component that functions to increase the uniformity and peel strength of the obtained electrode and to increase the rate characteristics and cycle characteristics of the obtained secondary battery.
[0050] As described above, the polymer β needs to contain 70.0% by mass or more and 95.0% by mass or less of the nitrile group-containing monomer units, with the total repeating units contained in the polymer β being 100% by mass. Furthermore, the polymer β preferably contains 80.0% by mass or more of the nitrile group-containing monomer units. If the proportion of the nitrile group-containing monomer units in the polymer β is equal to or more than the above lower limit, the polymer β is easily adsorbed to the electrode active material when the slurry composition is prepared, and the electrode active material can be well coated with a thin film. This can improve the battery characteristics of the obtained secondary battery. Furthermore, if the proportion of the nitrile group-containing monomer units in the polymer β is equal to or less than the above upper limit, the flexibility of the obtained electrode can be further improved.
[0051] Examples of nitrile group-containing monomers that can be used to form the nitrile group-containing monomer unit include α,β-ethylenically unsaturated nitrile monomers. Specifically, examples of α,β-ethylenically unsaturated nitrile monomers include acrylonitrile; α-halogenoacrylonitriles such as α-chloroacrylonitrile and α-bromoacrylonitrile; α-alkylacrylonitriles such as methacrylonitrile and α-ethylacrylonitrile; and the like. These can be used alone or in combination of two or more. Among these, acrylonitrile and methacrylonitrile are preferred, and acrylonitrile is more preferred, from the viewpoint of increasing the binding force that can be exerted by the polymer β and increasing the peel strength of the obtained electrode. These can be used alone or in combination of two or more.
[0052] Furthermore, as described above, the polymer β needs to contain at least one of an amide group-containing monomer unit and a (meth)acrylic acid ester monomer unit having an alkyl chain with 1 to 6 carbon atoms in addition to the nitrile group-containing monomer unit. In particular, it is preferable that the polymer β contains both an amide group-containing monomer unit and a (meth)acrylic acid ester monomer unit having an alkyl chain with 1 to 6 carbon atoms inclusive. The total content of the amide group-containing monomer unit and the (meth)acrylic acid ester monomer unit in the polymer β needs to be 0.1 to 20% by mass, preferably 0.5% by mass or more, more preferably 1% by mass or more, and preferably 15% by mass or less, based on 100% by mass of all repeating units.
[0053] The amide group-containing monomer unit can be formed using an amide group-containing monomer. The amide group-containing monomer is not particularly limited, and examples thereof include N-vinylacetamide, (meth)acrylamide, N-methylol(meth)acrylamide, dimethyl(meth)acrylamide, diethyl(meth)acrylamide, N-methoxymethyl(meth)acrylamide, and dimethylaminopropyl(meth)acrylamide. Among them, the amide group-containing monomer used to form the polymer β is preferably (meth)acrylamide, and more preferably acrylamide. The content ratio of the amide group-containing monomer unit in the polymer β may be 0% by mass, based on the total repeating units being 100% by mass, and is preferably 0.05% by mass or more, more preferably 0.1% by mass or more, even more preferably 0.5% by mass or more, even more preferably 1.0% by mass or more, and is preferably 5% by mass or less, and more preferably 2% by mass or less. If the content ratio of the amide group-containing monomer unit is equal to or more than the above lower limit, the flexibility and peel strength of the obtained electrode can be further increased.
[0054] The (meth)acrylic acid ester monomer unit having an alkyl chain carbon number of 1 or more and 6 or less can be formed using a (meth)acrylic acid ester monomer having an alkyl chain carbon number of 1 or more and 6 or less. Examples of the (meth)acrylic acid ester monomer having an alkyl chain carbon number of 1 or more and 6 or less include, among the (meth)acrylic acid alkyl ester monomers listed in the item of <Polymer α>, those having an alkyl chain carbon number of 1 or more and 6 or less, that is, acrylic acid alkyl esters such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, t-butyl acrylate, pentyl acrylate, hexyl acrylate, etc.; methacrylic acid alkyl esters such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, t-butyl methacrylate, pentyl methacrylate, hexyl methacrylate, etc. Among these, from the viewpoint of imparting an appropriate affinity with the electrolyte to the resulting electrode mixture layer, a (meth)acrylic acid alkyl ester having a linear alkyl chain is preferred, and butyl acrylate is more preferred. These may be used alone or in combination of two or more. The content ratio of the (meth)acrylic acid ester monomer unit having 1 to 6 carbon atoms in the polymer β may be 0 mass%, preferably 0.05 mass% or more, more preferably 0.1 mass% or more, even more preferably 1 mass% or more, preferably 20 mass% or less, and more preferably 15 mass% or less, based on the total repeating units being 100 mass%. If the content ratio of the (meth)acrylic acid ester monomer unit having 1 to 6 carbon atoms is equal to or more than the above lower limit, the flexibility and peel strength of the resulting electrode can be further increased.
[0055] Furthermore, the polymer β may contain other monomer units such as ethylenically unsaturated acid monomer units in addition to the above-mentioned monomer units. The monomer that can be used to form the ethylenically unsaturated acid monomer units is not particularly limited, and various monomers listed in the section of <Polymer α> can be used. The content of the ethylenically unsaturated acid monomer units in the polymer β is, for example, preferably 0.1% by mass or more, more preferably 1% by mass or more, preferably 10% by mass or less, and more preferably 5% by mass or less, based on 100% by mass of all repeating units.
[0056] The polymer β has a weight average molecular weight of preferably 200,000 or more, more preferably 400,000 or more, and even more preferably 600,000 or more, and preferably 2,000,000 or less, more preferably 1,500,000 or less, and even more preferably 1,300,000 or less. When the weight average molecular weight of the polymer β is equal to or greater than the lower limit, the peel strength of the resulting electrode can be further increased. When the weight average molecular weight of the polymer γ is equal to or less than the upper limit, the rate characteristics and cycle characteristics of the resulting secondary battery can be improved.
[0057] The polymer β is not particularly limited, and can be prepared, for example, according to a known method as described in the section [Method for preparing polymer α].
[0058] <Polymer γ> The polymer γ is a component that can function to further increase the flexibility and uniformity of the resulting electrode. The polymer γ, together with the polymer α and the polymer β, can function as a binder in the electrode mixture layer. The polymer γ is a component that is easily soluble in the organic solvent that constitutes the binder composition. The polymer γ is "easily soluble" in the organic solvent means that the dry mass of the insoluble portion obtained by leaving the dried polymer γ in N-methyl-2-pyrrolidone at a temperature of 60° C. for 72 hours and filtering through a 200 mesh is 50% by mass or less with respect to the total mass of the dried polymer γ used. If the binder composition contains the polymer γ as a binder component, the flexibility and uniformity of the resulting electrode can be further increased. If the binder composition contains the polymer γ as a binder component, the peel strength of the resulting electrode can be increased.
[0059] The iodine value of the polymer γ is 5 g / 100 g or more and 100 g / 100 g or less, preferably 10 g / 100 g or more, and more preferably 20 g / 100 g or more. When the iodine value of the polymer γ is equal to or more than the lower limit, the flexibility of the obtained electrode can be further improved. When the iodine value of the polymer γ is equal to or less than the upper limit, the uniformity and peel strength of the obtained electrode can be further improved.
[0060] The weight average molecular weight of the polymer γ is preferably 5,000 or more, more preferably 70,000 or more, and even more preferably 100,000 or more, and is preferably 500,000 or less, more preferably 400,000 or less, and even more preferably 350,000 or less. When the weight average molecular weight of the polymer γ is equal to or more than the lower limit, the peel strength of the obtained electrode can be further increased. When the weight average molecular weight of the polymer γ is equal to or less than the upper limit, the rate characteristics and cycle characteristics of the obtained secondary battery can be improved.
[0061] The composition of the polymer γ is not particularly limited as long as it satisfies the above-mentioned range of iodine value, and may be any composition. Among them, the polymer γ preferably contains an aromatic vinyl monomer unit, a nitrile group-containing monomer unit, an ethylenically unsaturated acid monomer unit, and a linear alkylene structural unit having 4 or more carbon atoms.
[0062] Examples of monomers that can be used to form the aromatic vinyl monomer unit include aromatic vinyl monomers such as styrene, α-methylstyrene, butoxystyrene, vinyltoluene, and vinylnaphthalene. The aromatic vinyl monomer does not contain an acidic group. These can be used alone or in combination of two or more. Among them, styrene is preferred from the viewpoint of good copolymerizability. The content of the aromatic vinyl monomer unit in the polymer γ is preferably 30% by mass or more, more preferably 35% by mass or more, and even more preferably 40% by mass or more, and preferably 55% by mass or less, more preferably 50% by mass or less, and even more preferably 45% by mass or less, when the total repeating units (the total of the structural units and the monomer units) of the polymer γ is taken as 100% by mass.
[0063] In addition, examples of monomers that can be used to form the nitrile group-containing monomer unit include the same monomers as those listed in the above item of <Polymer β>. These can be used alone or in combination of two or more. Among these, from the viewpoint of increasing the binding strength that can be exhibited by the polymer γ, acrylonitrile and methacrylonitrile are preferred, and acrylonitrile is more preferred. These can be used alone or in combination of two or more. The content ratio of the nitrile group-containing monomer unit in the polymer γ is preferably 10% by mass or more, more preferably 13% by mass or more, even more preferably 18% by mass or more, preferably 40% by mass or less, more preferably 33% by mass or less, and even more preferably 28% by mass or less, when the total repeating units are taken as 100% by mass.
[0064] In addition, as a monomer that can be used to form the ethylenically unsaturated acid monomer unit, the same monomers as those listed in the item [ethylenically unsaturated acid monomer unit] of the above <Polymer α> can be used. Among them, acrylic acid and methacrylic acid are preferable, and methacrylic acid is more preferable, because they can efficiently capture transition metal ions that may be eluted from the positive electrode active material. The content ratio of the ethylenically unsaturated acid monomer unit in the polymer γ is preferably 0.1% by mass or more, more preferably 1% by mass or more, preferably 10% by mass or less, and more preferably 6% by mass or less, when the total repeating units are 100% by mass.
[0065] Here, the linear alkylene structural unit having 4 or more carbon atoms (hereinafter, also simply referred to as "alkylene structural unit") is a linear alkylene structural unit having 4 or more carbon atoms represented by the general formula: -C n H 2n - [wherein n is an integer of 4 or more]. The method for introducing the linear alkylene structural unit having 4 or more carbon atoms into the polymer γ is not particularly limited, but may be, for example, the following method (1) or (2): (1) A method in which a polymer is prepared from a monomer composition containing a conjugated diene monomer, and the polymer is hydrogenated to convert the conjugated diene monomer unit into a linear alkylene structural unit having 4 or more carbon atoms. (2) A method for preparing a polymer from a monomer composition containing a 1-olefin monomer having 4 or more carbon atoms, such as 1-butene or 1-hexene. These conjugated diene monomers and 1-olefin monomers can be used alone or in combination of two or more kinds. Among these, method (1) is preferred since the polymer can be easily produced.
[0066] Examples of the conjugated diene monomer that can be used in the above method (1) include conjugated diene compounds having 4 or more carbon atoms, such as 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, and 1,3-pentadiene. These can be used alone or in combination of two or more. Among them, 1,3-butadiene is preferred. That is, the linear alkylene structural unit having 4 or more carbon atoms is preferably a structural unit (conjugated diene hydrogenated unit) obtained by hydrogenating a conjugated diene monomer unit, and more preferably a structural unit (1,3-butadiene hydrogenated unit) obtained by hydrogenating a 1,3-butadiene unit. The selective hydrogenation of the conjugated diene monomer unit can be carried out using a known method such as an oil layer hydrogenation method or an aqueous layer hydrogenation method.
[0067] The polymer γ is not particularly limited, and can be prepared, for example, by polymerizing a monomer composition containing the above-mentioned monomers to obtain a copolymer, and then hydrogenating (adding hydrogen) the obtained copolymer as necessary.
[0068] In polymer γ, the content of linear alkylene structural units having 4 or more carbon atoms, when all repeating units are taken as 100% by mass, is preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more, and is preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less. In addition, when the linear alkylene structural unit having 4 or more carbon atoms contained in the polymer γ is formed by a method of preparing a polymer from a monomer composition containing a conjugated diene monomer and hydrogenating the polymer, it is preferable that the total content of the linear alkylene structural unit having 4 or more carbon atoms contained in the polymer γ and the conjugated diene monomer unit remaining in the polymer γ without being hydrogenated satisfies the above range.
[0069] <Content of Polymers α to γ> Here, the contents of the polymers α to γ that satisfy the above-mentioned property and / or composition conditions in the binder composition are preferably within the following ranges, respectively, assuming the content of the binder component in the binder composition to be 100 mass %. First, the content a of the polymer α is preferably 5% by mass or more, more preferably 10% by mass or more, preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 40% by mass or less, and particularly preferably 30% by mass or less. If the content a of the polymer α is equal to or more than the lower limit, the flexibility of the electrode formed using the binder composition can be sufficiently increased. Also, if the content a of the polymer α is equal to or less than the upper limit, the peel strength of the obtained electrode can be increased.
[0070] Furthermore, the content b of the polymer β described above is preferably 20% by mass or more, more preferably 30% by mass or more, even more preferably 35% by mass or more, even more preferably 40% by mass or more, and preferably 94% by mass or less. If the content b of the polymer β is equal to or more than the lower limit, the uniformity of the obtained electrode can be improved, and the cycle characteristics of the secondary battery including such an electrode can be improved. If the content b of the polymer β is equal to or less than the upper limit, the rate characteristics of the obtained secondary battery can be improved.
[0071] The content c of the polymer γ is preferably 0.1% by mass or more, more preferably 1% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 30% by mass or less, and particularly preferably 20% by mass or less. If the content c of the polymer γ is equal to or greater than the lower limit, the flexibility, uniformity, and peel strength of the resulting electrode can be further improved. If the content c of the polymer γ is equal to or less than the upper limit, the battery characteristics of the resulting secondary battery can be further improved.
[0072] <Interrelationship between contents a~c> The content a of the polymer α and the content b of the polymer β are preferably such that the value of the ratio (%) of the polymer α to the total content of the polymers α and β represented by the formula: a / (a+b)×100 satisfies: 10≦a / (a+b)×100≦50, more preferably satisfies 10≦a / (a+b)×100≦40, and even more preferably satisfies 10≦a / (a+b)×100≦35. If the value of the above formula: a / (a+b)×100 is 10 or more, the polymer α can be used to point-bond the adherend components with sufficient frequency, and the flexibility of the obtained electrode mixture layer can be further improved. In addition, if the value of the above formula: a / (a+b)×100 is 50 or less, the uniformity of the obtained electrode can be improved, and the rate characteristics and cycle characteristics of the obtained secondary battery can be further improved.
[0073] In addition, the content a of polymer α and the content c of polymer γ, which is the ratio (%) of polymer α to the total content of polymer α and γ expressed by the formula: a / (a+c)×100, preferably satisfies 20≦a / (a+c)×100≦90, and more preferably satisfies 50≦a / (a+c)×100≦90. If the value of the above formula: a / (a+c)×100 is 20 or more, the peel strength of the obtained electrode mixture layer can be further increased. In addition, if the value of the above formula: a / (a+c)×100 is 90 or less, the rate characteristics of the obtained secondary battery can be further improved.
[0074] <Solubility of Polymers α and β in NMP> The above-mentioned polymers α and β are preferably polymers that satisfy the requirement that when an N-methyl-2-pyrrolidone mixed solution having a solid content concentration of 8 mass% containing the polymer α at a content rate a and the polymer β at a content rate b as solid contents is prepared, the proportion of the insoluble content in the mixed solution is 30 mass% or more and 80 mass% or less. And, the proportion of the insoluble content of the polymers α and β is more preferably 35 mass% or more and 75 mass% or less. If the proportion of the insoluble content is 30 mass% or more, the flexibility of the obtained electrode mixture layer can be further improved. Also, if the proportion of the insoluble content is 80 mass% or less, the rate characteristic and cycle characteristic of the obtained secondary battery can be improved.
[0075] <Other binders> The binder composition of the present invention may contain, as other binder components, other binder materials different from the above-mentioned polymers α-γ. Examples of such binder materials include fluorine-based polymer binders such as polyvinylidene fluoride, polyvinyl acetate binders, polyacrylic acid binders, polyvinyl alcohol binders, etc. In addition, when the binder composition of the present invention contains other binder components, the content ratio of such other binder components is preferably less than 50 mass%, more preferably 40 mass% or less, and even more preferably 30 mass% or less, based on the mass of all binder components contained in the binder composition being 100 mass%, and may be 0 mass%, that is, the binder composition of the present invention may contain only the above-mentioned polymers α-γ as binder components.
[0076] <Plasticizer> The plasticizer acts on the polymer contained as a binder component to increase the flexibility of the resulting electrode, which in turn functions to improve the rate characteristics and cycle characteristics of the secondary battery. The plasticizer also acts to protect the surface of the electrode active material in the resulting electrode. In this respect, the plasticizer is also a component that can act to improve the battery characteristics of the secondary battery. The plasticizer of the binder composition of the present invention is not particularly limited, and various compounds can be used. More specifically, the plasticizer may be diphenyl octyl phosphate, tributyl phosphate, trimethyl phosphate, tricresyl phosphate, triphenyl phosphate, trixylenyl phosphate, tri-2-ethylhexyl phosphate, 2-ethylhexyl diphenyl phosphate, trisisopropylphenyl phosphate, resorcinol bisdiphenyl phosphate, bisphenol A bisdiphenyl phosphate, bisphenol A biscresyl phosphate, 2-ethylhexyl diphenyl phosphate, trisisopropylphenyl phosphate, resorcinol bisdiphenyl phosphate, bisphenol A bisdiphenyl phosphate, bisphenol A biscresyl phosphate, 2-ethylhexyl diphenyl phosphate, bisphenol A bisdi ... phosphate ester plasticizers such as ethylhexyl diphenyl phosphate, citrate ester plasticizers such as tributyl citrate and acetyl tributyl citrate, epoxy plasticizers such as epoxidized soybean oil and epoxidized linseed oil, di(butoxyethoxyethyl) phthalate, dibutoxyethyl isophthalate, di(butoxyethoxyethyl) isophthalate, dimethoxyethyl phthalate, dibutyl phthalate, dioctyl phthalate, diisononyl phthalate, diisodecyl phthalate, diundecyl phthalate, butyl benzyl (Iso)phthalate ester plasticizers such as phthalate, dimethoxyethyl phthalate, diethoxyethyl phthalate, dibutoxyethyl phthalate, di-(2-ethylhexyl) phthalate, diisobutyl phthalate, diheptyl phthalate, dicyclohexyl phthalate, diphenyl phthalate, butyl benzyl phthalate, di-(2-ethylhexyl) isophthalate, and diisooctyl isophthalate; di-(2-ethylhexyl) tetrahydrophthalate, di-n-octyl tetrahydrophthalate, and diisodecyl tetrahydrophthalate; tetrahydrophthalic acid ester plasticizers; adipate ester plasticizers such as dibutoxyethyl adipate, di(butoxyethoxyethyl) adipate, di-2-hexyl adipate, di-(2-ethylhexyl) adipate, diisodecyl adipate, diisononyl adipate, dibutyl adipate; sebacate ester plasticizers such as dibutoxyethyl sebacate, di(butoxyethoxyethyl) sebacate, di-n-butyl sebacate, di-(2-ethylhexyl) sebacate, di-2-ethylhexyl sebacate;Azelaic acid ester-based plasticizers such as dibutoxyethyl azelaate, di(butoxyethoxyethyl) azelaate, di-(2-ethylhexyl) azelaate, diisooctyl azelaate, di-n-hexyl azelaate, and di-2-hexyl azelate; trimellitic acid ester-based plasticizers such as tri-2-ethylhexyl trimellitate; fumaric acid ester-based plasticizers such as dibutyl fumarate; oleic acid ester-based plasticizers such as butyl oleate; polyester-based plasticizers; trimellitic acid derivatives such as tri-(2-ethylhexyl) trimellitate, tri-n-octyl trimellitate, triisodecyl trimellitate, triisooctyl trimellitate, tri-n-hexyl trimellitate, triisononyl trimellitate, and triisodecyl trimellitate can be used. Examples of the plasticizer include compounds obtained by esterification of alkanedicarboxylic acids such as succinic acid, glutaric acid, adipic acid, suberic acid, and azelaic acid with alcohols having an ether bond in the molecule such as methoxytriethoxyethanol, methoxytetraethoxyethanol, butoxytriethoxyethanol, pentoxytetraethoxyethanol, ethoxytripoxypropanol, and ethoxytetrapentoxypentanol, and the alkyl chain contains 4 or more carbon atoms. Among them, preferred plasticizers include compounds containing an alkyl chain having 4 or more carbon atoms and at least one polar group selected from a phosphoric acid group, a carbonyl group, and a hydroxyl group. In particular, the plasticizer is preferably a phosphoric acid ester plasticizer, and more preferably 2-ethylhexyl diphenyl phosphate. The number of carbon atoms in the alkyl chain contained in the plasticizer is not particularly limited and may be 10 or less.
[0077] A compound that can be suitably contained as a plasticizer and that contains an alkyl chain having 4 or more carbon atoms and at least one polar group selected from a phosphate group, a carbonyl group, and a structure represented by the general formula R-OH (R is a saturated or unsaturated hydrocarbon chain) has high affinity with the (meth)acrylic acid ester monomer unit contained in the above-mentioned polymer α, the (meth)acrylic acid ester monomer unit that can be contained in the polymer β, the nitrile group-containing monomer unit that can be contained in the polymer β, and the nitrile group-containing monomer unit that can be contained in the optional polymer γ, and has a polar group, so that it tends to accompany the binder components such as polymers α and β in a binder composition using an organic solvent as a dispersion medium. Therefore, when an electrode mixture layer is formed using the binder composition, it can be uniformly dispersed in the electrode mixture layer and well retained in the electrode mixture layer. Furthermore, when a secondary battery is formed using an electrode having such an electrode mixture layer, it is considered that the plasticizer tends not to migrate to the electrolyte side. Therefore, by blending a compound containing an alkyl chain having 4 or more carbon atoms and at least one polar group selected from a phosphate group, a carbonyl group, and a structure represented by the general formula R-OH (R is a saturated or unsaturated hydrocarbon chain) as a plasticizer in the binder composition, the flexibility of the obtained electrode can be favorably increased, and deterioration of the battery characteristics, such as the rate characteristics and cycle characteristics, of the obtained secondary battery can be effectively suppressed.
[0078] The molecular weight of the plasticizer is preferably 1000 or less, more preferably 900 or less, and preferably 100 or more, and more preferably 200 or more. If the molecular weight of the plasticizer is equal to or less than the upper limit, the flexibility of the resulting electrode can be further increased. If the molecular weight of the plasticizer is equal to or more than the lower limit, the peel strength of the resulting electrode can be further increased.
[0079] The decomposition potential of the plasticizer is preferably 3.5 V or more, more preferably 4.0 V or more. The decomposition potential may usually be 10 V or less. If the decomposition potential of the plasticizer is equal to or more than the above lower limit, the rate characteristics and cycle characteristics of the obtained secondary battery can be further improved.
[0080] In addition, the plasticizer preferably has a higher boiling point than the organic solvent contained in the binder composition. The boiling point of the plasticizer refers to the boiling point at 1 atm. If the boiling point of the plasticizer is higher than the boiling point of the organic solvent, the plasticizer can be prevented from volatilizing when heated and dried during the manufacture of the electrode, and the plasticizer can be satisfactorily retained in the electrode mixture layer. Furthermore, the plasticizer is preferably a substance that is liquid at room temperature (25°C).
[0081] Furthermore, the content of the plasticizer in the binder composition is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1.2% by mass or more, preferably 30% by mass or less, more preferably 15% by mass or less, and even more preferably 12% by mass or less, based on the total content of the binder component and the plasticizer being 100% by mass. If the content of the plasticizer is equal to or more than the lower limit, the flexibility of the obtained electrode can be further increased. If the content of the plasticizer is equal to or less than the upper limit, the peel strength of the obtained electrode can be increased. If the content of the plasticizer is equal to or less than the upper limit, the rate characteristic and cycle characteristic of the obtained secondary battery can be further improved.
[0082] <Organic solvent> Examples of the organic solvent for the binder composition of the present invention include alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, t-butanol, pentanol, hexanol, heptanol, octanol, nonanol, decanol, and amyl alcohol, ketones such as acetone, methyl ethyl ketone, and cyclohexanone, esters such as ethyl acetate and butyl acetate, ethers such as diethyl ether, dioxane, and tetrahydrofuran, amide polar organic solvents such as N,N-dimethylformamide and N-methyl-2-pyrrolidone (NMP), and aromatic hydrocarbons such as toluene, xylene, chlorobenzene, orthodichlorobenzene, and paradichlorobenzene. These may be used alone or in combination of two or more. Among these, the organic solvent is preferably NMP.
[0083] <Other ingredients> In addition to the above components, the binder composition of the present invention may contain components such as a reinforcing material, a leveling agent, a viscosity modifier, and an electrolyte additive. These are not particularly limited as long as they do not affect the battery reaction, and known components, such as those described in International Publication No. 2012 / 115096, can be used. In addition, these components may be used alone or in combination of two or more types in any ratio.
[0084] <Preparation of Binder Composition> The binder composition of the present invention can be prepared by mixing the above-mentioned polymers α and β as binder components, a plasticizer, an organic solvent, and any other components by a known method. Specifically, the binder composition can be prepared by mixing the above-mentioned components using a mixer such as a ball mill, a sand mill, a bead mill, a pigment disperser, a crusher, an ultrasonic disperser, a homogenizer, a planetary mixer, or a film mix. The solid content concentration of the binder composition is not particularly limited and can be, for example, 5% by mass or more and 60% by mass or less.
[0085] (Slurry Composition for Non-aqueous Secondary Battery Electrodes) The slurry composition for non-aqueous secondary battery electrodes of the present invention contains an electrode active material, a conductive material, and the above-described binder composition, and optionally further contains other components. That is, the slurry composition of the present invention contains an electrode active material, a conductive material, the above-described polymers α and β, a plasticizer, and an organic solvent, and optionally further contains other components. And since the slurry composition of the present invention contains the above-described binder composition, it is possible to simultaneously achieve, at a high level, forming an electrode excellent in flexibility and uniformity, and enhancing the rate characteristics and cycle characteristics of a secondary battery provided with the obtained electrode. Hereinafter, as an example, the case where the slurry composition for secondary battery electrodes is a slurry composition for a positive electrode of a lithium-ion secondary battery will be described, but the present invention is not limited to the following example.
[0086] <Electrode Active Material> An electrode active material is a substance that transfers electrons in the electrodes of a secondary battery. And as a positive electrode active material for a lithium-ion secondary battery, usually, a substance capable of occluding and releasing lithium is used.
[0087] Specifically, the positive electrode active material for a lithium-ion secondary battery is not particularly limited, and includes lithium-containing cobalt oxide (LiCoO2), lithium manganate (LiMn2O4), lithium-containing nickel oxide (LiNiO2), lithium-containing composite oxide of Co-Ni-Mn (Li(Co Mn Ni)O2), lithium-containing composite oxide of Ni-Mn-Al, lithium-containing composite oxide of Ni-Co-Al, olivine-type lithium iron phosphate (LiFePO4), olivine-type lithium manganese phosphate (LiMnPO4), Li2MnO3-LiNiO2-based solid solution, Li 1+x Mn 2-x O4 (0 <X <2) spinel compound with excess lithium represented by, Li[Ni 0.17 Li 0.2 Co 0.07 Mn 0.56 O2, LiNi 0.5 Mn 1.5Examples of the positive electrode active material include known positive electrode active materials such as O4. The particle size of the positive electrode active material is not particularly limited and can be the same as that of a conventionally used positive electrode active material. The content of the positive electrode active material in the slurry composition can be, for example, 90% by mass or more and 99% by mass or less, assuming that the total solid content in the slurry composition is 100% by mass.
[0088] <Conductive material> The conductive material is for ensuring electrical contact between the electrode active materials. The slurry composition of the present invention preferably contains carbon nanotubes (CNTs), which are fibrous carbon materials, as the conductive material. The binder composition of the present invention described above allows CNTs to be dispersed well in the slurry composition, which in turn increases the dispersibility of other solid contents, such as the electrode active material, in the slurry composition. Examples of CNTs include single-walled or multi-walled carbon nanotubes (multi-walled carbon nanotubes include cup-stacked types). The specific surface area of CNTs is 50 m 2 / g or more, and 2 / g or more is more preferable, and 100m 2 / g or more is more preferable, and 2 / g or less, and 2 / g or less is more preferable, and 2 / g or less is more preferable. If the specific surface area of the CNT is within the above range, good dispersibility of the CNT in the slurry composition can be ensured, and the viscosity of the slurry composition can be stabilized. In the present invention, the "specific surface area" refers to the nitrogen adsorption specific surface area measured by the BET method. Further, as a conductive material other than CNT, carbon black (for example, acetylene black, Ketjen Black (registered trademark), furnace black, etc.), carbon nanohorn, milled carbon fiber obtained by crushing after firing polymer fiber, single-layer or multi-layer graphene, conductive carbon materials such as carbon nonwoven fabric sheet obtained by firing nonwoven fabric made of polymer fiber; fibers or foils of various metals, etc. may be further included. These can be used alone or in combination of two or more. In addition, the particle size of the conductive material is not particularly limited and can be the same as that of a conventionally used conductive material. The content ratio of the conductive material in the slurry composition can be, for example, 0.1% by mass or more and 3% by mass or less, assuming that the total solid content in the slurry composition is 100% by mass.
[0089] <Binder composition> The binder composition is the binder composition for a non-aqueous secondary battery electrode of the present invention described above. The content of the binder composition in the slurry composition can be, for example, 0.1% by mass or more and 5% by mass or less, based on 100% by mass of the total solid content in the slurry composition.
[0090] <Other ingredients> Other components that can be added to the slurry composition are not particularly limited, and include the same components as those that can be added to the binder composition of the present invention. In addition, the other components may be used alone or in combination of two or more kinds in any ratio.
[0091] <Method for producing slurry composition> The above-mentioned slurry composition can be produced, for example, by dissolving or dispersing each of the above-mentioned components in an organic solvent. More specifically, the above-mentioned slurry composition of the present invention can be prepared by performing the operation of adding each of the above-mentioned components to an organic solvent in multiple stages, or by adding the required components to an organic solvent in one operation. When performing the operation of adding the blended components to an organic solvent in multiple stages, the order of addition and the combination of the added components are not particularly limited.
[0092] The mixing method when adding the blending components to the organic solvent is not particularly limited, and examples thereof include mixing methods using a mixer such as a ball mill, a sand mill, a bead mill, a pigment disperser, a crusher, an ultrasonic disperser, a homogenizer, a planetary mixer, or a Filmix.
[0093] The organic solvent may be the same as the organic solvent that can be blended in the binder composition of the present invention. The organic solvent used in the production of the slurry composition may be the organic solvent contained in the binder composition. The total amount of the various components added in the production of the slurry composition is as described in detail in the sections (Binder composition for non-aqueous secondary battery electrode) and (Slurry composition for non-aqueous secondary battery electrode).
[0094] Also, for example, the slurry composition may be prepared by first preparing a binder particle aggregate containing polymers α and β, and a plasticizer, as described in the section below entitled “Method for producing a slurry composition using a binder particle aggregate,” and then using the binder particle aggregate.
[0095] <<Method for producing a slurry composition using binder particle aggregates>> In the method for producing a slurry composition using a binder particle aggregate, a slurry composition can be produced using a binder particle aggregate prepared by spray drying an aqueous dispersion (hereinafter sometimes referred to as "slurry for binder particles") that contains at least a plasticizer, polymer α and polymer β, and optionally contains polymer γ and other components. More specifically, for example, the binder particle aggregate prepared as described below can be mixed with an organic solvent, an electrode active material, a conductive material, and other optional components to obtain a slurry composition.
[0096] [Method for producing binder particle aggregate] In producing the binder particle aggregate, first, the binder particle slurry is sprayed into hot air and dried. Here, an atomizer can be used as a device for spraying the binder particle slurry. There are two types of atomizers: a rotating disk type and a pressure type. The rotating disk method is a method in which the binder particle slurry is introduced into the center of a disk rotating at high speed, and the binder particle slurry is discharged outside the disk by the centrifugal force of the disk, thereby atomizing the binder particle slurry. In the rotating disk method, the rotation speed of the disk is not particularly limited, but is preferably 5,000 rpm or more and 30,000 rpm or less. The pressurizing method is a method in which the binder particle slurry is pressurized and discharged from a nozzle to atomize the binder particle slurry, and examples of the pressurized nozzle method include the pressurized two-fluid nozzle method, etc. In the pressurized two-fluid nozzle method, the air pressure (dispersion air pressure) discharged from the air nozzle for finely adjusting the spray of the binder particle slurry is not particularly limited, but is preferably 0.01 MPa or more and 0.5 MPa or less.
[0097] The hot air temperature during spray drying is, for example, from 80° C. to 250° C. In addition, the method of blowing hot air during spray drying is not particularly limited, and any known method can be used.
[0098] (Electrode for non-aqueous secondary batteries) The electrode for a non-aqueous secondary battery of the present invention comprises an electrode mixture layer containing polymer α and polymer β as binder components, a plasticizer, an electrode active material, and a conductive material. Furthermore, the electrode for a non-aqueous secondary battery of the present invention may be an electrode in which the electrode mixture layer is formed on a current collector. The electrode mixture layer may be formed using the slurry composition of the present invention, or may be formed according to other methods as long as it contains the above-mentioned essential components. The electrode mixture layer may optionally contain polymer γ and other components. The electrode for a non-aqueous secondary battery of the present invention comprises an electrode mixture layer that satisfies the above-mentioned composition, and therefore has excellent flexibility and uniformity, and can improve the rate characteristics and cycle characteristics of the secondary battery.
[0099] The preferred ratio of each component contained in the electrode mixture layer is the same as the preferred ratio of each component in the slurry composition. The polymer α is a particulate polymer, and the particle shape can be confirmed when the electrode mixture layer is observed under magnification. The polymer β is preferably present in such a manner that it covers at least a part of the surface of the solid component such as the electrode active material. Furthermore, the optional component polymer γ is preferably present in such a manner that it is adjacent to the CNT. Details of the polymers α to γ are as described in the section (Binder composition).
[0100] <Electrode manufacturing method> The electrode for a nonaqueous secondary battery of the present invention can be produced, for example, through a step of applying a slurry composition containing the above-mentioned predetermined components onto a current collector (application step) and a step of drying the slurry composition applied onto the current collector to form an electrode mixture layer on the current collector (drying step).
[0101] [Coating process] The method of applying the above-mentioned slurry composition onto the current collector is not particularly limited, and any known method can be used. Specifically, the application method can be a doctor blade method, a dip method, a reverse roll method, a direct roll method, a gravure method, an extrusion method, a brush coating method, or the like. In this case, the slurry composition may be applied to only one side of the current collector, or may be applied to both sides. The thickness of the slurry film on the current collector after application and before drying can be appropriately set according to the thickness of the electrode mixture layer obtained by drying.
[0102] Here, the current collector to which the slurry composition is applied is made of a material that is electrically conductive and electrochemically durable. Specifically, the current collector may be made of, for example, iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, platinum, etc. The above-mentioned materials may be used alone or in combination of two or more kinds in any ratio.
[0103] [Drying process] The method for drying the slurry composition on the current collector is not particularly limited and may be a known method, for example, a drying method using warm air, hot air, or low-humidity air, a vacuum drying method, or a drying method using irradiation with infrared rays or electron beams, etc. By drying the slurry composition on the current collector in this manner, an electrode mixture layer can be formed on the current collector, and a secondary battery electrode including the current collector and the electrode mixture layer can be obtained.
[0104] After the drying step, the electrode mixture layer may be subjected to a pressure treatment using a mold press or a roll press. The pressure treatment can improve the adhesion between the electrode mixture layer and the current collector. In addition, when the electrode mixture layer contains a curable polymer, it is preferable to cure the polymer after the electrode mixture layer is formed.
[0105] (Non-aqueous secondary battery) The nonaqueous secondary battery of the present invention includes the electrode for a nonaqueous secondary battery of the present invention. More specifically, the nonaqueous secondary battery of the present invention includes a positive electrode, a negative electrode, an electrolyte, and a separator, and uses the electrode for a nonaqueous secondary battery of the present invention as at least one of the positive electrode and the negative electrode. Since the nonaqueous secondary battery of the present invention includes the electrode for a nonaqueous secondary battery of the present invention, the nonaqueous secondary battery of the present invention has excellent battery characteristics such as rate characteristics and cycle characteristics. The non-aqueous secondary battery of the present invention preferably uses the non-aqueous secondary battery electrode of the present invention as a positive electrode. In the following, the case where the secondary battery is a lithium ion secondary battery will be described as an example, but the present invention is not limited to the following example.
[0106] <Electrode> Here, the electrodes other than the above-mentioned electrodes for non-aqueous secondary batteries that can be used in the non-aqueous secondary battery of the present invention are not particularly limited, and known electrodes used in the manufacture of non-aqueous secondary batteries can be used. Specifically, the electrodes other than the above-mentioned electrodes for non-aqueous secondary batteries can be electrodes formed by forming an electrode mixture layer on a current collector using a known manufacturing method.
[0107] <Electrolyte> As the electrolyte, an organic electrolyte in which a supporting electrolyte is dissolved in an organic solvent is usually used. As the supporting electrolyte of the lithium ion secondary battery, for example, a lithium salt is used. As the lithium salt, for example, LiPF6, LiAsF6, LiBF4, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, (C2F5SO2)NLi, etc. are listed. Among them, LiPF6, LiClO4, and CF3SO3Li are preferred, and LiPF6 is particularly preferred, since they are easily dissolved in the solvent and show a high degree of dissociation. Note that one type of electrolyte may be used alone, or two or more types may be used in combination at any ratio. Usually, the lithium ion conductivity tends to be higher as the supporting electrolyte with a higher degree of dissociation is used, so the lithium ion conductivity can be adjusted by the type of supporting electrolyte.
[0108] The organic solvent used in the electrolytic solution is not particularly limited as long as it can dissolve the supporting electrolyte, but for example, carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), and ethyl methyl carbonate (EMC); esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfur-containing compounds such as sulfolane and dimethyl sulfoxide; and the like are preferably used. A mixture of these solvents may also be used. Among them, carbonates are preferably used because they have a high dielectric constant and a wide stable potential range, and a mixture of ethylene carbonate and diethyl carbonate is more preferably used. The concentration of the electrolyte in the electrolytic solution can be appropriately adjusted. The electrolytic solution can also contain known additives such as vinylene carbonate.
[0109] <separator> The separator is not particularly limited, and may be one described in, for example, JP 2012-204303 A. Among these, a microporous film made of a polyolefin resin (polyethylene, polypropylene, polybutene, polyvinyl chloride) is preferred, since it can reduce the thickness of the entire separator, thereby increasing the ratio of the electrode active material in the secondary battery and increasing the capacity per volume.
[0110] <Method of manufacturing non-aqueous secondary battery> The non-aqueous secondary battery of the present invention can be produced, for example, by stacking a positive electrode and a negative electrode with a separator therebetween, wrapping or folding the stack according to the shape of the battery as necessary, placing the stack in a battery container, injecting an electrolyte into the battery container, and sealing the container. In order to prevent the occurrence of an internal pressure rise in the secondary battery, overcharging and discharging, etc., a fuse, an overcurrent prevention element such as a PTC element, an expanded metal, a lead plate, etc. may be provided as necessary. The shape of the secondary battery may be, for example, any of a coin type, a button type, a sheet type, a cylindrical type, a square type, a flat type, etc. EXAMPLES
[0111] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following description, the units "%" and "parts" expressing amounts are by mass unless otherwise specified. In addition, in a polymer produced by copolymerizing multiple types of monomers, the ratio of monomer units formed by polymerizing a certain monomer in the polymer usually coincides with the ratio (feed ratio) of that certain monomer to all monomers used in the polymerization of the polymer, unless otherwise specified. In the examples and comparative examples, the attributes of the plasticizer, the NMP solubility of the polymers α to γ, the iodine value of the polymer γ, the weight average molecular weights of the polymers β and γ, and the proportion of the NMP insoluble content of the mixture of the polymers α and β were measured or confirmed as follows. In the examples and comparative examples, the electrode flexibility, electrode uniformity, peel strength of the electrode mixture layer, initial capacity of the secondary battery, rate characteristics, and cycle characteristics were evaluated as follows.
[0112] <Properties of plasticizers> The molecular weight of the plasticizer was measured by LC-MS (Liquid Chromatography Mass Spectrometry), and the decomposition potential was measured by CV (Cyclic Voltammetry) described below. A plasticizer solution was obtained by adding a plasticizer to a 1M LiPF6 solution (solvent: ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 3 / 7 (volume ratio)) so that the solid concentration was 0.2 mass%. Metallic Li and glassy carbon were placed as reference electrodes in this plasticizer solution, and the starting point of the rise in the current value when the voltage was changed at an insertion rate of 2 mV / s was taken as the decomposition potential. <NMP solubility of polymer α (confirmation that it is an insoluble polymer)> The polymer α prepared in the examples and comparative examples was vacuum dried for 24 hours in a 25°C environment to obtain a dried polymer (mass: W1g). The obtained dried polymer was left in NMP at 60°C for 72 hours, and then filtered with a 200 mesh (75μm) to separate the insoluble portion. The insoluble portion was washed with methanol and then dried for 24 hours in a 25°C environment to obtain a dried insoluble portion (mass: W2g). From the above W1 and W2, the NMP insoluble portion of the polymer α (=W2 / W1×100 (mass%)) was calculated. Then, it was confirmed that the NMP insoluble portion of the polymer α prepared in all the examples and comparative examples was 70% by mass or more. Therefore, it was confirmed that the polymer α used was an "insoluble polymer".
[0113] <NMP solubility of polymers β and γ (confirmation that they are readily soluble polymers)> The NMP solubility of the polymers β and γ was confirmed according to the following procedure. 25 g of the composition containing polymer β / γ in N-methyl-2-pyrrolidone (NMP) prepared in the examples and comparative examples was dropped into 1 L of methanol to precipitate polymer β / γ. The precipitated polymer β / γ was vacuum dried for 24 hours in a 25°C environment to obtain a dried polymer β / γ (mass: W1 g). The obtained dried polymer β / γ was left in NMP at 60°C for 72 hours, and then filtered through a 200 mesh to separate the insoluble portion. The insoluble portion was washed with methanol and then dried for 24 hours in a 25°C environment to obtain a dried insoluble portion (mass: W2 g). From the above W1 and W2, the NMP insoluble portion of polymer β / γ (= W2 / W1 × 100 (mass%)) was calculated. It was confirmed that the NMP insoluble portion of the polymer β / γ prepared in all examples was 50 mass% or less. In addition, in the comparative examples, it was confirmed that the polymers β and γ other than the polymer β prepared in Comparative Example 1 had an NMP insoluble content of 50 mass % or less.
[0114] <Iodine value of polymer γ> 100 g of the aqueous dispersion of polymer γ prepared in the Examples and Comparative Examples (before the solvent was replaced with NMB) was coagulated with 1 L of methanol, and then vacuum dried for 12 hours at a temperature of 60° C. The iodine value of the dried readily soluble polymer γ thus obtained was measured according to JIS K6235 (2006). <Weight-average molecular weight of polymers β and γ> The weight average molecular weights of the polymers β and γ prepared in the examples and comparative examples were measured by gel permeation chromatography (GPC). Specifically, a calibration curve was prepared using polystyrene as a standard substance, and the weight average molecular weights were calculated as a standard substance equivalent value. The measurement conditions were as follows. <<Measurement conditions>> Measuring Equipment Column: TSKgel α-M x 2 (φ7.8mm I.D. x 30cm x 2, Tosoh Corporation) Measurement conditions Eluent: Dimethylformamide (50 mM lithium bromide, 10 mM phosphoric acid) Flow rate: 0.5mL / min. Sample concentration: Approximately 0.5g / L (solid concentration) Injection volume: 200μL Column temperature: 40℃ Detector: Differential refractive index detector RI (Tosoh HLC-8320 GPC RI detector) Detector conditions: RI: Pol(+), Res(1.0s) Molecular weight marker: Tosoh Corporation standard polystyrene kit PStQuick K
[0115] <Ratio of NMP insoluble content in mixture of polymers α and β> In an environment at 25° C., the polymers α and β or alternative components prepared in the Examples and Comparative Examples were added to an NMP solvent in the mixing ratio described in the Examples so that the solid content concentration was 8%, to prepare 100 g of a (polymers α and β)-NMP mixture. The prepared mixture was filtered through a wire net with 80 mesh (180 μm), the filtrate was weighed, and the ratio (mass%) of the mass of the insoluble matter to the total solid content added was calculated.
[0116] <Electrode flexibility> Rods of different diameters were placed on the positive electrode composite layer side of the positive electrode for lithium ion secondary batteries prepared in the Examples and Comparative Examples, and the positive electrode was wound around the rod to evaluate whether the positive electrode composite layer cracked. The smaller the diameter of the rod that does not crack the positive electrode composite layer when the positive electrode is wound around the rod, the more flexible the positive electrode is and the better the winding properties are. The flexibility of the electrode (positive electrode) was evaluated according to the following criteria, depending on the diameter of the thinnest rod that did not crack the positive electrode composite layer. A: It will not break even if wrapped around a rod with a diameter of 1.15 mm. B: It does not break even when wrapped around a rod with a diameter of 1.40 mm. C: It does not break even when wrapped around a rod with a diameter of 2.00 mm. D: It will not break even if wrapped around a rod with a diameter of 3.00 mm. <Electrode uniformity> The electrode uniformity was evaluated based on the uniformity of the film thickness of the electrode mixture layer. 2The film thickness was measured at five points inside the battery, and the variation in film thickness was evaluated. The smaller the variation in film thickness, the more uniform the movement of lithium inside the battery becomes, and the lower the resistance becomes. A: In-plane variation is less than 1.5% B: In-plane variation is 1.5% or more and less than 3% C: In-plane variation is 3% or more and less than 5% D: In-plane variation is 5% or more
[0117] <Peel strength of electrode mixture layer> The positive electrodes for lithium ion secondary batteries prepared in the examples and comparative examples were cut into a rectangle of 100 mm in length and 10 mm in width to prepare test pieces, and cellophane tape (compliant with JIS Z1522) was attached to the surface of the positive electrode composite layer with the surface having the positive electrode composite layer facing down, and one end of the current collector was pulled vertically and peeled off at a speed of 100 mm / min to measure the stress (note that the cellophane tape was fixed to the test table). The measurement was performed three times, and the average value was calculated as the peel strength, which was evaluated according to the following criteria. The larger the peel strength value, the stronger the adhesion between the positive electrode composite layer and the current collector, and the higher the peel strength of the electrode (positive electrode) composite layer. A: Peel strength is 30N / m or more B: Peel strength is 25N / m or more and less than 30N / m C: Peel strength is 20N / m or more and less than 25N / m D: Peel strength is less than 20N / m <Initial capacity of secondary battery> The lithium ion secondary battery prepared in the examples and comparative examples was left at rest for 5 hours at 25°C after injecting the electrolyte. Next, it was charged to a cell voltage of 3.65V at a constant current of 0.2C at a temperature of 25°C, and then aged for 12 hours at a temperature of 60°C. Then, it was discharged to a cell voltage of 3.00V at a constant current of 0.2C at a temperature of 25°C. Then, it was CC-CV charged (upper cell voltage 4.20V) at a constant current of 0.2C, and CC discharged to a cell voltage of 3.00V at a constant current of 0.2C. This charge and discharge at 0.2C was repeated three times. The third discharge capacity was taken as the initial capacity, and the value of the initial capacity / theoretical capacity was evaluated according to the following criteria. The higher this value, the higher the initial discharge capacity. A: Initial capacity / theoretical capacity is 0.78 or more B: Initial capacity / theoretical capacity is 0.75 or more and less than 0.78 C: Initial capacity / theoretical capacity is 0.73 or more and less than 0.75 D: Initial capacity / theoretical capacity is less than 0.73 <Rate characteristics of secondary batteries> The lithium ion secondary batteries prepared in the examples and comparative examples were left to stand at 25°C for 5 hours after injecting the electrolyte. Next, the batteries were charged to a cell voltage of 3.65V at a constant current of 0.2C at 25°C, and then aged at 60°C for 12 hours. Then, the batteries were discharged to a cell voltage of 3.00V at a constant current of 0.2C at 25°C. Then, CC-CV charging (upper cell voltage 4.20V) was performed at a constant current of 0.2C, and CC discharging was performed at a constant current of 0.2C to a cell voltage of 3.00V. This charging and discharging at 0.2C was repeated three times. Next, in an environment at a temperature of 25°C, constant current charging and discharging of 0.2C was performed at a cell voltage between 4.20 and 3.00V, and the discharge capacity at this time was defined as C0. Thereafter, similarly, CC-CV charging was performed at a constant current of 0.2C, and CC discharging was performed at a constant current of 2.0C to 3.00V in an environment at a temperature of 25°C, and the discharge capacity at this time was defined as C1. Then, as the rate characteristic, the ratio (percentage, capacity retention rate) of the discharge capacity (C1) at 2.0C to the discharge capacity (C0) at 0.2C, which is represented by (C1 / C0) x 100 (%), was obtained and evaluated according to the following criteria. The larger the value of this capacity retention rate, the smaller the decrease in discharge capacity at high current and the lower the internal resistance (i.e., the better the rate characteristic). A: Capacity retention rate is 75% or more B: Capacity retention rate is 73% or more but less than 75% C: Capacity retention rate is 70% or more but less than 73% D: Capacity retention rate is less than 70% <Cycle characteristics of secondary batteries> The lithium ion secondary battery prepared in the examples and comparative examples was left at rest for 5 hours at 25°C after injecting the electrolyte. Next, the battery was charged to a cell voltage of 3.65V at a constant current of 0.2C at a temperature of 25°C, and then aged for 12 hours at a temperature of 60°C. Then, the battery was discharged to a cell voltage of 3.00V at a constant current of 0.2C at a temperature of 25°C. Then, the battery was CC-CV charged (upper cell voltage 4.20V) at a constant current of 0.2C, and CC discharged to a cell voltage of 3.00V at a constant current of 0.2C. This charge and discharge at 0.2C was repeated three times. Then, 100 cycles of charge and discharge were performed at a cell voltage of 4.20-3.00V and a charge and discharge rate of 1.0C in an environment of 35°C. At that time, the discharge capacity of the first cycle was defined as X1, and the discharge capacity of the 100th cycle was defined as X2. Using the discharge capacity X1 and the discharge capacity X2, the capacity retention rate (the ratio of the discharge capacity at the 100th cycle to the discharge capacity at the 1st cycle) was calculated as the cycle characteristic, expressed as (X2 / X1)×100(%), and evaluated according to the following criteria: A higher capacity retention rate indicates better cycle characteristics. A: Capacity retention rate is 93% or more B: Capacity retention rate is 90% or more but less than 93% C: Capacity retention rate is 87% or more but less than 90% D: Capacity retention rate is less than 87%
[0118] Example 1 <Preparation of Polymer α> 100 parts of ion-exchanged water was added to a 1 L flask equipped with a stirrer and a septum, the gas phase was replaced with nitrogen gas, and the temperature was raised to 80°C. After that, 0.3 parts of ammonium persulfate (APS) was dissolved in 5.7 parts of ion-exchanged water as a polymerization initiator and added. Meanwhile, in a separate container, 40 parts of ion-exchanged water, 0.18 parts of sodium polyoxyethylene alkyl ether sulfate (manufactured by Kao Chemical Co., Ltd., "Latemul E-118B") as an emulsifier, 55 parts of methyl methacrylate and 39 parts of n-butyl acrylate as (meth)acrylic acid ester monomers, 5 parts of methacrylic acid as an ethylenically unsaturated acid monomer, and 1 part of allyl methacrylate as a crosslinkable monomer were mixed to obtain a monomer composition. This monomer composition was continuously added to the 1 L flask with a septum over 1 hour to carry out polymerization. During the addition, the reaction was carried out at 80°C. After the addition was completed, the mixture was further stirred at 80°C for 1 hour to terminate the reaction. Next, an appropriate amount of NMP was added to the obtained aqueous dispersion of polymer α to obtain a mixture, which was then distilled under reduced pressure at 90° C. to remove water and excess NMP from the mixture, thereby obtaining an NMP dispersion of polymer α (solid content: 8%). The obtained NMP dispersion of polymer α was dried at 120°C for 1 hour to prepare a film with a thickness of 0.2 mm to 0.5 mm. A scanning electron microscope (SEM) was used to confirm that the polymer α maintained its particulate form, thereby confirming that particulate polymer α was dispersed in the dispersion medium (NMP).
[0119] <Preparation of polymer β1> In a reactor A equipped with a mechanical stirrer and a condenser, 85 parts of ion-exchanged water and 0.2 parts of sodium dodecylbenzenesulfonate were placed under a nitrogen atmosphere. The contents were heated to 55°C while stirring, and a 5.0% aqueous solution of 0.3 parts of potassium persulfate was added to the reactor A. Next, in a vessel B equipped with a mechanical stirrer other than the reactor A, 92 parts of acrylonitrile as a nitrile group-containing monomer, 1 part of acrylamide as an amide group-containing monomer, 2 parts of methacrylic acid as an ethylenically unsaturated acid monomer, and 5 parts of butyl acrylate as a (meth)acrylic acid ester monomer, as well as 0.6 parts of sodium dodecylbenzenesulfonate, 0.035 parts of tertiary dodecyl mercaptan, 0.4 parts of polyoxyethylene lauryl ether, and 80 parts of ion-exchanged water were added under a nitrogen atmosphere, and the mixture was emulsified by stirring to prepare a monomer mixture. Then, this monomer mixture was added to reactor A at a constant rate over 5 hours while being stirred and emulsified, and reacted until the polymerization conversion rate reached 95%, to obtain an aqueous dispersion of a nitrile polymer (polymer β1) mainly containing acrylonitrile units (92% by mass). Next, an appropriate amount of NMP was added to the aqueous dispersion of the obtained polymer β1 to obtain a mixture. After that, reduced pressure distillation was performed at 90°C to remove water and excess NMP from the mixture, and an NMP solution of polymer β1 (solid concentration: 8%) was obtained.
[0120] <Preparation of polymer γ1> In an autoclave equipped with a stirrer, 240 parts of ion-exchanged water, 25 parts of sodium alkylbenzenesulfonate as an emulsifier, 24 parts of acrylonitrile as a nitrile group-containing monomer, 43 parts of styrene as an aromatic vinyl monomer, and 4 parts of methacrylic acid as an ethylenically unsaturated acid monomer were placed in this order, and the inside was replaced with nitrogen. Then, 29 parts of 1,3-butadiene as a conjugated diene monomer were pressed in, and 0.25 parts of ammonium persulfate as a polymerization initiator was added to carry out a polymerization reaction at a reaction temperature of 40°C, thereby obtaining a copolymer containing a nitrile group-containing monomer unit, an aromatic vinyl monomer unit, an ethylenically unsaturated acid monomer unit, and a conjugated diene monomer unit. The iodine value of the obtained copolymer (pre-hydrogenation polymer) was measured according to the above, and was 140g / 100g. The polymerization conversion rate was 85%. Ion-exchanged water was added to the polymer before hydrogenation to obtain 400 mL of a solution (total solid content 48 g) adjusted to a total solid content concentration of 12 mass%. The solution was placed in a 1 L autoclave equipped with a stirrer, and nitrogen gas was passed through for 10 minutes to remove dissolved oxygen in the solution. Then, 50 mg of palladium acetate was dissolved in 180 ml of ion-exchanged water containing 4 times the molar amount of nitric acid relative to palladium (Pd) as a hydrogenation reaction catalyst and added. After replacing the system twice with hydrogen gas, the contents of the autoclave were heated to 50°C while pressurizing with hydrogen gas to 3 MPa in gauge pressure, and hydrogenation reaction (first stage hydrogenation reaction) was carried out for 6 hours. Next, the pressure inside the autoclave was returned to atmospheric pressure, and 25 mg of palladium acetate was dissolved in 60 ml of water containing 4 times the molar amount of nitric acid relative to Pd as a hydrogenation catalyst and added. After replacing the inside of the system with hydrogen gas twice, the contents of the autoclave were heated to 50°C while pressurizing with hydrogen gas up to a gauge pressure of 3 MPa, and hydrogenation reaction (second-stage hydrogenation reaction) was carried out for 6 hours. Thereafter, the contents were returned to room temperature, the inside of the system was conditioned with nitrogen, and the contents were then concentrated using an evaporator until the solid concentration reached 40%, to obtain an aqueous dispersion of polymer γ1 as polymer γ. To 100 parts of the aqueous dispersion of polymer γ1 obtained above, 320 parts of N-methylpyrrolidone (hereinafter referred to as "NMP") was added as a solvent, and water was evaporated under reduced pressure to obtain an NMP dispersion of polymer γ1.
[0121] <Production of slurry composition for secondary battery positive electrode> In this example, a slurry composition was prepared according to slurry composition preparation method I (referred to as "Preparation Method I" in Table 1) involving the following operations. [Premixing process] For the disperser, one CNT was used as a conductive material (specific surface area measured according to the BET method: 150 m 2 Predetermined amounts of 1000g / g, multilayer type) and polymer γ1 were added, and further, NMP (boiling point: 204°C) was added as an organic solvent so that the solid concentration was 4 mass%, and the mixture was stirred at a temperature of 25±3°C and a rotation speed of 3000 rpm for 10 minutes to obtain a premixture. [Main mixing process] The premix obtained in the above process was mixed with the lithium composite oxide active material NMC532, LiNi 5 / 10 Co 2 / 10 Mn 3 / 10 To the mixture were added 97 parts of O2), 0.15 parts of 2-ethylhexyl diphenyl phosphate as a plasticizer, and predetermined amounts of polymer α and polymer β, and further NMP was added as necessary. The mixture was stirred and mixed at a temperature of 25±3°C and a rotation speed of 50 rpm to obtain a slurry composition for a positive electrode having a viscosity of 3,600 mPa s as measured using a Brookfield viscometer at 60 rpm (rotor M4) and 25±3°C. In the above premixing step and main mixing step, the total amount of the binder components (that is, the polymers α to γ) and the plasticizer was 2 parts per 97 parts by mass of the positive electrode active material. The blending amount of the binder component and the blending amount of the plasticizer were adjusted so that the blending amount of the plasticizer was 7.5% by mass, with the total mass of the plasticizer and the binder component being 100% by mass. Furthermore, the blending amounts of the binder components (i.e., polymers α to γ) were adjusted so that the content of the binder components was 100 mass%, the content a of polymer α was 19 mass%, the content b of polymer β was 78 mass%, and the content c of polymer γ was 3 mass%.
[0122] <Production of positive electrodes> The slurry composition for positive electrodes obtained as described above was applied to a 20 μm-thick aluminum foil current collector with a comma coater in an amount of 20±0.5 mg / cm. 2 The coating was applied so that the result was as follows. The slurry composition on the aluminum foil was dried by transporting the aluminum foil at a speed of 200 mm / min through an oven at a temperature of 100° C. for 2 minutes and then through an oven at a temperature of 130° C. for 2 minutes, thereby obtaining a positive electrode raw sheet in which a positive electrode composite layer was formed on the current collector. Thereafter, the positive electrode composite layer side of the prepared positive electrode blank was roll-pressed under conditions of a temperature of 25±3°C and a linear pressure of 14 tonnes, so that the density of the positive electrode composite layer became 3.50 g / cm 3 The positive electrode thus obtained was subjected to the peel strength evaluation of the positive electrode mixture layer according to the above-mentioned method. The results are shown in Table 1.
[0123] <Preparation of binder composition for negative electrode> In a 5MPa pressure vessel equipped with a stirrer, 64 parts of styrene, 33 parts of 1,3-butadiene, 2 parts of itaconic acid, 1 part of 2-hydroxyethyl acrylate, 0.3 parts of t-dodecyl mercaptan as a molecular weight regulator, 5 parts of sodium dodecylbenzenesulfonate as an emulsifier, 150 parts of ion-exchanged water, and 1 part of potassium persulfate as a polymerization initiator were added, thoroughly stirred, and then heated to a temperature of 55°C to initiate polymerization. When the monomer consumption reached 95.0%, the reaction was stopped by cooling. A 5% aqueous solution of sodium hydroxide was added to the aqueous dispersion containing the polymer thus obtained, and the pH was adjusted to 8. Thereafter, unreacted monomers were removed by heating and reduced pressure distillation. Thereafter, the temperature was cooled to 30°C or less to obtain an aqueous dispersion containing a binder for the negative electrode. <Preparation of Slurry Composition for Negative Electrode> Into a planetary mixer, 48.75 parts of artificial graphite (theoretical capacity: 360mAh / g) as a negative electrode active material, 48.75 parts of natural graphite (theoretical capacity: 360mAh / g), and 1 part of carboxymethylcellulose as a thickener in terms of solid content were added. Further, the mixture was diluted with ion-exchanged water so that the solid content concentration was 60%, and then kneaded for 60 minutes at a rotation speed of 45 rpm. Then, 1.5 parts of the negative electrode binder composition obtained above in terms of solid content were added, and kneaded for 40 minutes at a rotation speed of 40 rpm. Then, ion-exchanged water was added so that the viscosity was 3000±500mPa·s (measured with a B-type viscometer at 25°C and 60 rpm), to prepare a negative electrode slurry composition. <Production of negative electrodes> The negative electrode slurry composition was applied to the surface of a 15 μm-thick copper foil current collector with a comma coater in an amount of 11±0.5 mg / cm 2 Thereafter, the copper foil coated with the negative electrode slurry composition was transported at a speed of 400 mm / min through an oven at a temperature of 80° C. for 2 minutes and then through an oven at a temperature of 110° C. for 2 minutes to dry the slurry composition on the copper foil, thereby obtaining a negative electrode raw sheet having a negative electrode mixture layer formed on a current collector. Thereafter, the negative electrode composite layer side of the produced negative electrode blank was roll-pressed under conditions of a temperature of 25±3°C and a linear pressure of 11 t (tons) to obtain a negative electrode composite layer density of 1.60 g / cm 3 A negative electrode of 1000 nm was obtained.
[0124] <Preparation of separator for secondary battery> A single-layer polypropylene separator (manufactured by Celgard, "#2500") was used.
[0125] <Preparation of non-aqueous secondary battery> Using the above negative and positive electrodes and separators, a single-layer laminate cell (equivalent to an initial design discharge capacity of 40 mAh) was fabricated and placed in an aluminum package. Then, a 1.0 M LiPF6 solution (solvent: mixed solvent of ethylene carbonate (EC) / diethyl carbonate (DEC) = 3 / 7 (volume ratio), additive: containing 2 volume% vinylene carbonate (solvent ratio)) was filled as the electrolyte. Furthermore, in order to seal the opening of the aluminum package, the aluminum package was closed by heat sealing at a temperature of 150°C, and a lithium-ion secondary battery was produced. The initial capacity, rate characteristics, and cycle characteristics of this lithium ion secondary battery were evaluated as described above. The results are shown in Table 1. When the positive electrode mixture layer of the obtained secondary battery was observed by SEM, a particulate polymer was confirmed.
[0126] Example 2 In this example, a slurry composition was prepared according to slurry composition preparation method II (referred to as "Preparation Method II" in Table 1) involving the following operations. The aqueous dispersion of polymer α obtained in Example 1, the aqueous dispersion of polymer β1, and the aqueous dispersion of polymer γ1, and 2-ethylhexyl diphenyl phosphate as a plasticizer were mixed in the ratio shown in Table 1 (slurry for binder particles), and the mixture was spray-dried using a spray dryer (manufactured by Niro, GEA) to prepare a binder particle aggregate. Two parts of the obtained binder particle aggregate were adjusted with NMP so that the solid content concentration was 6%, and one part of CNT (specific surface area measured according to the BET method: 150 m) was added as a conductive material. 2 / g) and Co-Ni-Mn lithium composite oxide active material NMC532, LiNi 5 / 10 Co 2 / 10 Mn 3 / 10 97 parts of O2) and NMP as an organic solvent were added, and the mixture was stirred and mixed at a temperature of 25±3°C for 60 minutes to disperse the binder, conductive material, and active material. A slurry composition for positive electrodes was obtained with a viscosity of 3,600 mPa s measured using a B-type viscometer at a rotation speed of 60 rpm (rotor M4) and 25±3°C.
[0127] Then, using the obtained positive electrode slurry composition, a positive electrode was produced in the same manner as in Example 1, and further, a negative electrode, a separator, and a nonaqueous secondary battery were also produced in the same manner as in Example 1, and various evaluations and measurements were performed. The results are shown in Table 1.
[0128] Example 3 Polymer γ2 was obtained by changing the hydrogenation reaction conditions during the preparation of polymer γ so that the iodine value would be the value shown in Table 1. Except for this, various operations, measurements, and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 1.
[0129] Example 4 Except for using polymer β2 prepared as described below as polymer β, various operations, measurements, and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 1. <Preparation of polymer β2> Except for the addition of 72 parts of acrylonitrile, 8 parts of acrylamide, 2 parts of methacrylic acid, and 18 parts of n-butyl acrylate to the reactor B, an aqueous dispersion of polyacrylonitrile (PAN) copolymer (polymer β2) having an acrylonitrile unit content of 72% by mass was obtained in the same manner as in Example 1. Then, in the same manner as in Example 1, the solvent was replaced with NMP to obtain an NMP solution of polymer β2 (solid concentration: 8%).
[0130] (Examples 5 to 6) Except for changing the blending amount of the plasticizer as shown in Table 1, various operations, measurements, and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 1.
[0131] (Examples 7 to 9) Various operations, measurements, and evaluations were carried out in the same manner as in Example 1, except that the types of plasticizers used were changed as shown in Table 1. The results are shown in Table 1.
[0132] Example 10 Various operations, measurements, and evaluations were carried out in the same manner as in Example 1, except that a component corresponding to polymer γ was not blended, and instead the content a of polymer α was changed as shown in Table 1. The results are shown in Table 1.
[0133] Example 11 Except for using polymer β3 prepared by using 1 part of methacrylamide instead of 1 part of acrylamide as the amide group-containing monomer as polymer β, various operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0134] Example 12 Various operations, measurements, and evaluations were performed in the same manner as in Example 1, except that polymer β4 prepared without using an amide group-containing monomer so as to have the composition shown in Table 1 was used as polymer β. The results are shown in Table 1.
[0135] Example 13 Various operations, measurements, and evaluations were performed in the same manner as in Example 1, except that polymer β5 prepared without using a (meth)acrylic acid ester monomer so as to have the composition shown in Table 1 was used as polymer β. The results are shown in Table 1.
[0136] Comparative Example 1 Various operations, measurements, and evaluations were performed in the same manner as in Example 1, except that no component corresponding to polymer β was blended, and instead polymer B1 was used, which was prepared so that the content ratio of acrylonitrile units, which are nitrile group-containing monomer units, was 40 mass%, so as to have the composition shown in Table 1. The results are shown in Table 1.
[0137] Comparative Example 2 Various operations, measurements, and evaluations were carried out in the same manner as in Example 1, except that no component corresponding to polymer α was used and the amounts of polymers β and γ were changed as shown in Table 1. The results are shown in Table 1.
[0138] Comparative Example 3 No component equivalent to a plasticizer was blended. The blending amounts of the polymers α to γ were changed so that the total blending amount was 2 parts relative to 97 parts of the electrode active material and the content ratios shown in Table 1 were satisfied. Except for these points, various operations, measurements, and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0139] Comparative Example 4 Except for not blending a component corresponding to polymer β and blending PVdF instead, various operations, measurements, and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 1.
[0140] Comparative Example 5 Various operations, measurements, and evaluations were carried out in the same manner as in Example 1, except that no component corresponding to polymer β was blended, and instead polymer B2 was used, which was prepared so that the content ratio of acrylamide units as amide group-containing monomer units was 25 mass%, so as to have the composition shown in Table 1. The results are shown in Table 1.
[0141] Comparative Example 6 Various operations, measurements, and evaluations were carried out in the same manner as in Example 1, except that no component corresponding to polymer β was blended, and instead polymer B3 prepared so as to have the composition shown in Table 1 was used. The results are shown in Table 1.
[0142] Comparative Example 7 Various operations, measurements, and evaluations were carried out in the same manner as in Example 1, except that no component corresponding to polymer β was blended, and instead polymer B4 prepared so as to have the composition shown in Table 1 was used. The results are shown in Table 1.
[0143] In addition, in Table 1 shown below, "MMA" stands for methyl methacrylate "BA" indicates n-butyl acrylate; "MAA" stands for methacrylic acid; "AMA" stands for allyl methacrylate; "AN" indicates acrylonitrile, "AAm" indicates acrylamide, "ST" indicates styrene, "H-BD" indicates a 1,3-butadiene hydride unit; "CNT" refers to carbon nanotubes.
[0144] [Table 1]
[0145] From Table 1, it can be seen that in Examples 1 to 13 using binder compositions containing the specified polymers α and β, it is possible to simultaneously achieve at a high level the formation of an electrode having excellent flexibility and uniformity, and the improvement of the rate characteristics and cycle characteristics of a secondary battery including the obtained electrode. Also, from Table 1, it can be seen that in Comparative Examples 1 to 2 and 4 to 7 lacking either polymer α or β, and Comparative Example 3 lacking a plasticizer, it is not possible to simultaneously achieve at a high level the formation of an electrode having excellent flexibility and uniformity, and the improvement of the rate characteristics and cycle characteristics of a secondary battery including the obtained electrode. [Industrial Applicability]
[0146] According to the present invention, it is possible to provide a binder composition for a non-aqueous secondary battery electrode and a slurry composition for a non-aqueous secondary battery electrode, which can simultaneously achieve, at a high level, the formation of an electrode having excellent flexibility and uniformity, and the improvement of the rate characteristics and cycle characteristics of a secondary battery including the obtained electrode. Furthermore, according to the present invention, it is possible to provide an electrode for a non-aqueous secondary battery, which has excellent flexibility and uniformity and can improve the rate characteristics and cycle characteristics of the secondary battery. Furthermore, according to the present invention, a nonaqueous secondary battery having excellent rate characteristics and cycle characteristics can be provided.
Claims
1. A binder composition for a non-aqueous secondary battery electrode, comprising polymer α and polymer β as binder components, a plasticizer, and an organic solvent, the polymer α is an insoluble polymer containing a (meth)acrylic acid ester monomer unit and an ethylenically unsaturated acid monomer unit, the polymer β is an easily soluble polymer containing a nitrile group-containing monomer unit and at least one of an amide group-containing monomer unit and a (meth)acrylic acid ester monomer unit having an alkyl chain carbon number of 1 to 6, and the content of the nitrile group-containing monomer unit is 70% by mass or more and 95% by mass or less, and the total content of the amide group-containing monomer unit and the (meth)acrylic acid ester monomer unit is 0.1% by mass or more and 20% by mass or less, relative to the total of all monomer units constituting the polymer β being 100% by mass; A binder composition for non-aqueous secondary battery electrodes.
2. The total mass of the binder components is taken as 100% by mass, 2. The binder composition for a non-aqueous secondary battery electrode according to claim 1, wherein the content a of the polymer α is 5 mass % or more and 60 mass % or less, and the content b of the polymer β is 20 mass % or more and 94 mass % or less.
3. The polymer α and the polymer β are When an N-methyl-2-pyrrolidone mixed solution containing, as solid contents, the polymer α at the content rate a and the polymer β at the content rate b, and having a solid content concentration of 8 mass%, is prepared, the mixed solution has an insoluble content rate of 30 mass% or more and 80 mass% or less. The binder composition for a non-aqueous secondary battery electrode according to claim 2 .
4. 4. The binder composition for a non-aqueous secondary battery electrode according to claim 1, wherein a content of the plasticizer is 0.1 mass% or more and 30 mass% or less, with the total mass of the plasticizer and the binder component being 100 mass%.
5. 5. The binder composition for a non-aqueous secondary battery electrode according to claim 1, wherein the plasticizer has a molecular weight of 1000 or less and a decomposition potential of 3.5 V or more.
6. The binder composition for a non-aqueous secondary battery electrode according to any one of claims 1 to 5, further comprising, as the binder component, a polymer γ which is an easily soluble polymer having an iodine value of 5 g / 100 g or more and 100 g / 100 g or less.
7. The binder composition for a non-aqueous secondary battery electrode according to claim 6 , wherein the content c of the polymer γ is 0.1 mass % or more and 50 mass % or less, based on 100 mass % of the content of the binder component.
8. A slurry composition for a non-aqueous secondary battery electrode, comprising an electrode active material, a conductive material, and the binder composition for a non-aqueous secondary battery electrode according to any one of claims 1 to 7.
9. The slurry composition for a non-aqueous secondary battery electrode according to claim 8 , wherein the conductive material comprises carbon nanotubes.
10. An electrode for a non-aqueous secondary battery, comprising an electrode mixture layer including polymer α and polymer β as binder components, a plasticizer, an electrode active material, and a conductive material, the polymer α is a particulate polymer containing a (meth)acrylic acid ester monomer unit and an ethylenically unsaturated acid monomer unit, the polymer β is an easily soluble polymer containing a nitrile group-containing monomer unit and at least one of an amide monomer unit and a (meth)acrylic acid ester monomer unit having an alkyl chain carbon number of 1 to 6, and the content of the nitrile group-containing monomer unit is 70% by mass or more and 95% by mass or less, and the total content of the amide group-containing monomer unit and the (meth)acrylic acid ester monomer unit is 0.1% by mass or more and 20% by mass or less, relative to 100% by mass of all monomer units constituting the polymer β; Electrode for non-aqueous secondary batteries.
11. 11. The electrode for a non-aqueous secondary battery according to claim 10, further comprising, as the binder component, a polymer γ that is an easily soluble polymer having an iodine value of 5 g / 100 g or more and 100 g / 100 g or less.
12. A non-aqueous secondary battery electrode having an electrode mixture layer formed using the slurry composition for a non-aqueous secondary battery electrode according to claim 8 or 9.
13. A non-aqueous secondary battery comprising the electrode for a non-aqueous secondary battery according to claim 10 or 11.
Citation Information
Patent Citations
Positive electrode paste, positive electrode plate and energy storage apparatus
CN108321360A
Slurry for preparing positive electrode of battery, electrode pole piece, preparation method thereof, and battery
CN109841835A
Slurry composition for electrode, electrode, and lithium ion secondary battery
JP2003132893A
Slurry composition for electrode, electrode and lithium-ion secondary battery
JP2004172017A
Slurry composition for electrode, electrode and secondary battery
JP2004185826A